Battery electrode recovery method and device
Through the ultrasonic cleaning liquid, the electrode layer and current collector are separated, combined with the circulating cleaning liquid and hydraulic cleaning technology, the problems of impurities affecting purity, high investment and low efficiency in the existing battery electrode recycling technology are solved, and efficient and environmentally friendly electrode recycling is achieved, and the recovered materials can be used for the preparation of new batteries.
Patent Information
- Application Number
- CN202311163223.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
AI Technical Summary
The existing battery electrode recycling technology has the problems of impurities affecting purity, high investment and low efficiency, and traditional methods have a great pollution to the environment.
Ultrasonic cleaning liquid is used to separate and recover the electrode layer and current collector. Through the recycling of the cleaning liquid and hydraulic cleaning technology, efficient recycling of electrode materials is achieved.
The electrode recovery rate is improved, the recycling cost is reduced, and the environmental pollution is reduced, and the recovered electrode materials can be used to prepare new batteries, showing excellent electrochemical properties.
Smart Images

Figure CN119601812A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery recycling, and in particular to a method and device for recycling battery electrodes. Background Art
[0002] Lithium-ion batteries are mainly composed of positive electrode, negative electrode, separator, electrolyte and casing, among which the electrode layer materials and current collector of positive and negative electrodes can be recycled.
[0003] During the battery manufacturing process, after the electrodes are coated with slurry, dried and rolled, they are cut according to the structure and specifications of the battery. After cutting, edge materials are produced, that is, the edge of the electrode, which will not be made into a battery. On the other hand, when manufacturing batteries, inferior products with poor performance and defects may be produced, which can also be recycled. In order to reduce waste, edge materials and defective products can be recycled to separate the electrode layer and current collector. These materials can be recycled and used again to make new electrodes, which helps to achieve a circular economy.
[0004] The current collector is usually a valuable metal or a valuable metal composite material. There are two main methods for processing battery electrodes: dry recovery and wet recovery. Dry recovery refers to the direct recovery of valuable metals without passing through a medium such as a solution. It mainly separates valuable metal materials from other substances through a series of operations such as crushing, screening, magnetic separation, fine grinding and classification. Wet recovery uses acid / alkaline solutions to dissolve the metal ions in the lithium battery, and then uses precipitation, adsorption and other means to extract the ions in the solution to separate them in the form of oxides, salts, etc. However, when using dry recovery, a small amount of impurities may still be mixed in the collected metal materials, affecting the purity; while wet recovery has high investment, low efficiency, and is prone to pollution, and it is not convenient to recover the metal after it is dissolved by the acid / alkaline solution.
[0005] The invention patent with the Chinese patent application publication number CN114665182A discloses a method for separating and recovering the current collector and the negative electrode material in the negative electrode of waste lithium-ion batteries. The method contacts the negative electrode of the battery with a stripping solution, and applies mechanical stirring and / or ultrasound for dissociation treatment to dissociate the negative electrode material and the current collector in the negative electrode. Although the stripping solution used can be recycled, the stripping solution contains organic solvents and surfactants, and also requires additional treatment with a lithium ion precipitant. When the stripping solution and the lithium ion precipitant reach the number of cycles and need to be discharged, the chemicals in the liquid will still cause pollution to the environment. In addition, the method also includes steps such as screening, centrifugation, and precipitation, and the process is complicated.
[0006] In view of the above, there is a need to develop a simple, efficient, economical and environmentally friendly method to recycle electrode materials and current collectors in electrodes. Summary of the invention
[0007] The above requirements are met by various aspects and embodiments disclosed in the present invention. The present invention provides a method for recycling battery electrodes, which comprises the following steps: a) wetting an electrode comprising a current collector and an electrode layer coated on one or both sides of the current collector with a cleaning solution; b) immersing the electrode in a cleaning solution and performing a first ultrasonic cleaning; c) taking out the electrode and rinsing it with a cleaning solution for the first time; d) immersing the electrode in a cleaning solution and performing a second ultrasonic cleaning; e) taking out the electrode and rinsing it for a second time with a cleaning solution to remove the electrode layer peeled off from the surface of its current collector; The electrode layer comprises a polymer binder and an electrode active material.
[0008] The present invention also provides a battery electrode recovery device, which can implement the method. The device includes a casing, a conveying device is arranged inside the casing, the conveying device includes a motor, a rotating shaft and a conveyor belt, the conveyor belt is installed on the rotating shaft, and under the drive of the motor, the battery electrodes on the conveyor belt pass through a first spraying device, a first groove, a second spraying device, a second groove, and a third spraying device arranged in the casing, and an ultrasonic generating device is arranged at the bottom of the first groove and the second groove.
[0009] Furthermore, a circulating water tank may be provided on the side of the recovery device, and the circulating water tank includes a first circulating water tank, a second circulating water tank, and a third circulating water tank. The first circulating water tank is respectively connected to the first groove and the first spray device, and the second circulating water tank is respectively connected to the second groove and the second spray device. The third circulating water tank is respectively connected to the third spray device and the second groove, and the third circulating water tank and the second circulating water tank are connected through a pipeline. The first circulating water tank and the second circulating water tank may be connected directly or through a pipeline. A valve may be provided on the pipeline.
[0010] Furthermore, the recycling device may be provided with a third groove, and the third groove is used to clean the electrode rinsed by the third spray device again. The third groove may be provided in a liquid cleaning mode or in a wind cleaning mode. When the third groove is provided in a liquid cleaning mode, the liquid in the third groove may be a cleaning liquid or other types of liquids. The third water tank may be provided to be connected to the third groove and the third spray device respectively, so as to realize the recycling of the cleaning liquid. A drying device may be provided after the third groove to dry the electrode after cleaning. The first water tank, the second water tank and the third water tank may be connected through a pipeline, and the pipeline may be provided with a valve.
[0011] When the third groove is set to the form of wind cleaning, since there is cleaning liquid remaining on the electrode surface at this time, the wind force needs to be adjusted according to the different specifications of the electrode to ensure that the wind can blow away the electrode material floating on the surface of the current collector. Furthermore, wind cleaning can regulate the temperature of the wind, which is conducive to faster drying of the current collector. Wind cleaning preferably uses a blowing device at normal temperature and low wind speed. Low wind speed will not blow away the electrode, and can prevent the metal from expanding and contracting due to heat and changing its shape, and can reduce the speed of metal oxidation.
[0012] The recovery device disclosed in the present invention can directly use the heated cleaning liquid, or a heating device can be arranged in the first groove and / or the second groove. To avoid conflict with the ultrasonic generating device, the heating device can be arranged on the side of the first groove and / or the second groove.
[0013] Furthermore, the first spray device is arranged above the conveyor belt, and the second spray device and the third spray device are arranged above and below the conveyor belt respectively. The spray head of the second spray device located below the conveyor belt needs to be arranged in a form that can adjust the angle, and the spray heads of other spray devices are arranged perpendicular to the conveyor belt.
[0014] In order to avoid the overlapping of pole pieces during spraying and wind cleaning, which affects the cleaning effect, a baffle can be set on the conveyor belt surface.
[0015] Furthermore, an observation water tank can be provided on the side of the recovery device. The observation water tank can be directly connected to the groove or connected to the circulating water tank through a pipeline, and the pipeline can be provided with a valve. The observation water tank is used to observe the turbidity of the cleaning liquid and the water level in the groove. When the cleaning liquid is obviously turbid or the solid-liquid ratio is greater than 30%, the cleaning liquid needs to be replaced. When the water level in the groove is too high, the electrode will float on the surface of the cleaning liquid, resulting in reduced electrode cleaning efficiency.
[0016] Furthermore, the casing includes a shell, which is a rectangular frame structure, and the shell is provided with a rectangular tube with a lower opening, the length direction of the rectangular tube is the same as the length direction of the shell, the rectangular tube is provided with an observation port, and a cover plate that can cover the observation port is provided on the observation port, and the rectangular tube is located in the middle section of the shell and has a length less than the length of the shell. A handle is provided on the cover plate, and the operation of the device can be observed by opening the cover plate, which is also convenient for the inspection and replacement of parts of the recovery device.
[0017] Furthermore, a control console is set on the side of the casing, which can control the following components: conveyor belt switch and speed adjustment, heating device switch and temperature adjustment, ultrasonic generator switch and current adjustment, spray device nozzle angle and water pressure adjustment, wind cleaning device / drying device switch and wind force adjustment, baffle status adjustment, etc.
[0018] The method disclosed in the present invention avoids complicated recycling processes, reduces recycling costs and reduces environmental pollution, while achieving excellent electrode recovery rates and recycling battery electrodes in an efficient manner. In addition, batteries prepared using electrode materials recycled using the method disclosed in the present invention exhibit excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Detailed description of the invention is a flow chart of an embodiment of the invention, illustrating the steps of recycling battery electrodes disclosed in the invention.
[0020] Figure 2 The current collector of the double-sided coated positive electrode in Example 1 is recovered after cleaning with a cleaning solution and ultrasonic cleaning.
[0021] Figure 3 The current collector of the double-sided coated positive electrode in Comparative Example 1 is recovered after cleaning with a cleaning solution and single-frequency ultrasonic cleaning.
[0022] Figure 4 The current collector of the double-sided coated positive electrode in Comparative Example 13 is recovered after cleaning with a cleaning solution and ultrasonic cleaning. DETAILED DESCRIPTION
[0023] The method disclosed in the present invention utilizes ultrasound to directly separate the electrode layer and the current collector, effectively improving the recovery rate. In addition, the use of ultrasonic equipment is low in cost and simple in operation. The treatment method of the cleaning liquid used to treat the electrode in the present invention can also solve environmental protection problems.
[0024] The term "electrode" refers to either a "positive electrode" or a "negative electrode".
[0025] The term "positive electrode" can be used interchangeably with "cathode". Similarly, the term "negative electrode" can be used interchangeably with "anode".
[0026] The term "polymer binder" refers to a chemical compound, mixture of compounds, or polymer used to hold electrode materials and / or conductive agents in place and adhere them to a metal component or current collector to form an electrode. In some embodiments, the metal component is conductive or non-conductive. In some embodiments, the electrode does not contain any conductive agent. In some embodiments, the polymer binder forms a colloid, solution, or dispersion in an aqueous solvent, such as water.
[0027] The term "conductive agent" refers to a material with good electrical conductivity. Therefore, the conductive agent is usually mixed with the electrode active material when forming the electrode to improve the conductivity of the electrode. In some embodiments, the conductive agent is chemically active. In some embodiments, the conductive agent is chemically inert.
[0028] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same or a different type. The generic term "polymer" embraces the terms "homopolymer" and "copolymer."
[0029] The term "homopolymer" refers to a polymer prepared by polymerizing the same type of monomers.
[0030] The term "copolymer" refers to polymers prepared by polymerizing two or more different types of monomers.
[0031] The term "ultrasound" refers to sound waves with a frequency higher than 20kHz, which is beyond the range of human hearing. Ultrasound is generated by the vibration of matter and can only propagate in a medium. When ultrasound reaches a substance, its action causes the molecules in the substance to vibrate, thereby allowing the molecules of the substance to gain energy. In one embodiment, the operating frequency is at least about 20kHz. In another embodiment, the operating frequency is at least about 28kHz. In yet another embodiment, the operating frequency is at least about 38kHz.
[0032] The term "cavitation" refers to the entire process of expansion, closure, and oscillation of small bubbles in a liquid under the action of ultrasound. When the tiny bubble nuclei in the liquid vibrate and the sound pressure reaches a certain value, small vacuum bubbles are generated in the liquid and the bubbles expand rapidly. When the bubble reaches a volume that can no longer absorb energy, it closes. During the rapid closure of the bubble, the liquid will reach very high temperatures and pressures locally, and shock waves will be generated.
[0033] The term "ultrasonic generator" refers to a device that can generate ultrasonic energy to clean an object. The ultrasonic generator emits high-frequency ultrasonic waves to impact the object, so that dirt, oil, water stains, resin and other impurities on the surface of the object are broken into small pieces and cleaned. Some non-limiting examples of ultrasonic generators include ultrasonic baths, ultrasonic vibration plates, and ultrasonic vibrators.
[0034] The term "ultrasonic bath" refers to a device that transmits ultrasonic energy to a liquid sample by means of a device that generates ultrasonic waves installed on the wall and / or the bottom of the container of the ultrasonic bath, or refers to a device that transmits ultrasonic energy to a liquid sample through the wall and / or the bottom of the container of the ultrasonic bath by means of a device that generates ultrasonic waves installed in the wall and / or the bottom of the container of the ultrasonic bath.
[0035] The term "ultrasonic vibrator" refers to a device that generates ultrasonic waves by generating regular vibrations.
[0036] The term "ultrasonic vibration plate" is a device capable of generating ultrasonic waves by a sheet-like block having high-frequency vibrations.
[0037] The term "constructive interference" refers to the phenomenon that when two or more coherent waves meet and superimpose in space, the amplitude of the superimposed wave changes periodically due to the differences in their wavelength, amplitude, phase and other characteristics. In the superimposed area, the area with larger amplitude is called the "enhancement area" and the area with smaller amplitude is called the "attenuation area".
[0038] The term "room temperature" refers to a room temperature of about 18°C to about 30°C, such as 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30°C. In some embodiments, room temperature refers to a temperature of about 20°C + / - 1°C, or + / - 2°C, or + / - 3°C. In other embodiments, room temperature refers to a temperature of about 22°C or about 25°C.
[0039] The term "apply" refers to the act of laying or spreading a substance on a surface.
[0040] The term "current collector" refers to any conductive substrate that is in contact with the electrode layer and can conduct current to the electrode during the discharge or charge of the secondary battery. Some non-limiting examples of current collectors include a single conductive metal layer or substrate and a single conductive metal layer or substrate covered with a conductive coating (e.g., a carbon black-based coating). The conductive metal layer or substrate can be in the form of a foil or a porous body with a three-dimensional mesh structure, and can be a polymer or a metallic material or a metallized polymer. In some embodiments, the three-dimensional porous current collector is covered with a conformal carbon layer.
[0041] The term "electrode layer" refers to a layer that is in contact with a current collector and contains an electrochemically active material. In some embodiments, the electrode layer is made by applying a coating on the current collector. In some embodiments, the electrode layer is located on the surface of the current collector. In other embodiments, the three-dimensional porous current collector is covered with a conformal electrode layer.
[0042] The term "unsaturated" refers to a moiety having one or more units of unsaturation.
[0043] The term "alkyl" or "alkyl group" refers to a radical having the general formula C n H 2n+1A monovalent group derived from a saturated, non-branched or branched aliphatic hydrocarbon removing a hydrogen atom, wherein n is an integer. The example of an alkyl group includes, but is not limited to, a C1-C8 alkyl group, such as a methyl, ethyl, propyl, isopropyl, 2-methyl-1-propyl, 2-methyl-2-propyl, 2-methyl-1-butyl, 3-methyl-1-butyl, 2-methyl-3-butyl, 2,2-dimethyl-1-propyl, 2-methyl-1-pentyl, 3-methyl-1-pentyl, 4-methyl-1-pentyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 2,2-dimethyl-1-butyl, 3,3-dimethyl-1-butyl, 2-ethyl-1-butyl, butyl, isobutyl, tert-butyl, pentyl, isopentyl, neopentyl, hexyl, heptyl and octyl. Longer alkyl groups include nonyl and decyl groups. An alkyl group can be unsubstituted or substituted with one or more suitable substituents.
[0044] The term "cycloalkyl" or "cycloalkyl group" refers to a saturated or unsaturated cyclic non-aromatic hydrocarbon group having a single ring or multiple condensed rings. Examples of cycloalkyl groups include, but are not limited to, C3-C7 cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cycloheptyl; C3-C7 cycloalkenyl groups such as cyclopropenyl, cyclobutenyl, cyclopentenyl, cyclohexenyl, and cycloheptenyl; and cyclic terpenes and bicyclic terpenes. The cycloalkyl group may be unsubstituted or substituted with one or two suitable substituents.
[0045] The term "alkoxy" refers to an alkyl group as defined above, connected to the main carbon chain by an oxygen atom. Some non-limiting examples of alkoxy groups include methoxy, ethoxy, propoxy, butoxy, etc. And the alkoxy group defined above can be substituted or unsubstituted, wherein the substituent can be, but is not limited to, deuterium, hydroxyl, amine, halogen, cyano, alkoxy, alkyl, alkenyl, alkynyl, mercapto, nitro, etc.
[0046] The term "alkenyl" refers to an unsaturated straight chain, branched or cyclic hydrocarbon group containing one or more carbon-carbon double bonds. Examples of alkenyl groups include, but are not limited to, vinyl, 1-propenyl or 2-propenyl, which may be optionally substituted on one or more carbon atoms of the group.
[0047] The term "aryl" or "aryl group" refers to an organic group derived from a monocyclic or polycyclic aromatic hydrocarbon by removing a hydrogen atom. Non-limiting examples of aryl groups include phenyl, naphthyl, benzyl, tolanyl, sexiphenyl, phenanthrenyl, anthracenyl, coronenyl and tolanylphenyl. The aryl group can be unsubstituted or substituted with one or more suitable substituents. In addition, the aryl group can be monocyclic or polycyclic. In some embodiments, the aryl group contains at least 6, 7, 8, 9 or 10 carbon atoms.
[0048] The term "aromatic" refers to a group comprising an aromatic hydrocarbon ring, which optionally includes heteroatoms or substituents. Examples of such groups include, but are not limited to, phenyl, tolyl, biphenyl, o-terphenyl, m-terphenyl, p-terphenyl, naphthyl, anthryl, phenanthryl, pyrenyl, triphenylene and derivatives thereof.
[0049] The term "substituted" as used to describe a compound or chemical moiety means that at least one of the hydrogen atoms of the compound or chemical moiety has been replaced by a second chemical moiety. The second chemical moiety is referred to as a "substituent". Examples of substituents include, but are not limited to, halogen; alkyl; heteroalkyl; alkenyl; alkynyl; aryl; heteroaryl; hydroxy; alkoxy; amine; nitro; thiol; thioether; imino; cyano; amide; phosphonato; phosphinyl; carboxyl; thiocarbonyl; sulfonyl; sulfonamide; acyl; formyl; acyloxy; alkoxycarbonyl; carbonyl; haloalkyl (e.g., trifluoroalkyl); methyl); carbocyclic cycloalkyl, which may be a monocyclic or fused or non-fused polycyclic (e.g., cyclopropyl, cyclobutyl, cyclopentyl or cyclohexyl), or heterocyclic alkyl, which may be a monocyclic or fused or non-fused polycyclic (e.g., pyrrolidinyl, piperidinyl, piperazinyl, morpholinyl or thiazinyl); carbocyclic or heterocyclic, monocyclic or fused or non-fused polycyclic aryl (e.g., phenyl, naphthyl, pyrrolyl, indolyl, furanyl, thienyl, thiazinyl); iophenyl), imidazolyl, oxazolyl, isoxazolyl, thiazolyl, triazolyl, tetrazolyl, pyrazolyl, pyridinyl, quinolyl, isoquinolyl, acridinyl, pyrazinyl, pyridazinyl, pyrimidinyl, benzimidazolyl, benzothiophenyl or benzofuranyl); amino (primary, secondary or tertiary); o-lower alkyl; o-aryl, aryl; aryl-lower alkyl; -CO2CH3; -CONH2; -OCH2CONH2; -NH2; -SO2NH2; -OCHF2; -CF3; -OCF3; -NH(alkyl); -N(alkyl)2; -NH(aryl); -N(alkyl)(aryl); -N(aryl)2; -CHO; -CO(alkyl); -CO(aryl); -CO2(alkyl); and -CO2(aryl); and these groups may also be optionally substituted with fused ring structures or bridge structures (e.g. -OCH2O-). These substituents may be optionally further substituted with substituents selected from these groups. Unless otherwise indicated, all chemical groups disclosed in the present invention may be substituted.
[0050] The term "halogen" or "halo" refers to F, Cl, Br or I.
[0051] The abbreviation "(meth)acrylic" includes both "acrylic" and "methacrylic".
[0052] The term "monomer unit" refers to a constitutional unit contributed to the structure of a polymer by a single monomer.
[0053] The term "structural unit" refers to the total monomer units provided by the same monomer type in a polymer.
[0054] The term "C-rate" refers to the charge or discharge rate of a battery expressed in ampere-hours (Ah) or milliampere-hours (mAh) based on its total storage capacity. For example, a 1C rate means that all the stored energy is used in one hour; 0.1C means that 10% of the energy is used in one hour or the entire energy is used in 10 hours; and 5C means that the entire energy is used in 12 minutes.
[0055] The term "Ah" refers to the unit used in describing the storage capacity of a battery. For example, a battery with a capacity of 1Ah can provide a current of 1 ampere for 1 hour or a current of 0.5 amperes for two hours, etc. Therefore, 1 Ah is equivalent to 3,600 coulombs of charge. Similarly, the term "milliampere-hour (mAh)" also refers to the unit used in describing the storage capacity of a battery and is 1 / 1,000 of an Ah.
[0056] The term "battery cycle life" refers to the number of complete charge / discharge cycles a battery can perform before its rated capacity decreases to less than 80% of its initial rated capacity.
[0057] The term "capacity" is a property of an electrochemical cell and refers to the total amount of charge that an electrochemical cell (e.g., a battery) can hold. Capacity is usually expressed in units of ampere-hours. The term "specific capacity" refers to the capacity output of an electrochemical cell (e.g., a battery) per unit weight, usually expressed in Ah / kg or mAh / g.
[0058] In the following description, all numerical values disclosed in the present invention are approximate values, regardless of whether the word "about" or "approximately" is used in conjunction with them. They may vary by 1%, 2%, 5% or sometimes 10% to 20%. Whenever a value with a lower limit R is disclosed, L and upper limit R U When a numerical range of R=R is specified, any value within the range is specifically disclosed. Specifically, the following values within the range are specifically disclosed: L +k*(R U -R L ), wherein k is a variable from 0% to 100%. Also, any numerical range defined by two R values determined in the above manner is also specifically disclosed.
[0059] The method disclosed in the present invention can be implemented by using a battery electrode recovery device. The cleaning device includes a housing, a conveying device is provided in the housing, the conveying device includes a motor, a rotating shaft and a conveyor belt, the conveyor belt is installed on the rotating shaft, and the battery electrodes on the conveyor belt are sequentially wetted by the first spray device in the housing under the drive of the motor, and then the first ultrasonic cleaning is performed through the first groove with the first ultrasonic generator, and then the first rinse is performed through the second spray device, and then the second ultrasonic cleaning is performed through the second groove with the second ultrasonic generator, and finally the second rinse is performed through the third spray device. If the method disclosed in the present invention needs to use a cleaning liquid higher than room temperature during the cleaning process, the heated cleaning liquid can be directly introduced, or a heating device can be provided in the first groove and / or the second groove to heat the cleaning liquid.
[0060] Using automation instead of manual operation can shorten the conversion time between each step, thereby improving the recovery rate and reducing the time required for the entire process. In addition, compared with manual operation, mechanical operation has a lower error rate and better recovery effect.
[0061] In some embodiments, in step 101, the electrode is wetted with a cleaning solution.
[0062] Generally, chemicals are used in the process of cleaning electrodes, which inevitably release toxic substances in the process, causing pollution to the environment, and there may be danger in handling these chemicals in the recycling process. In some embodiments, the cleaning solution can be an aqueous solvent. In some embodiments, the cleaning solution is an aqueous solvent comprising a main component and a secondary component, wherein the main component is water; and wherein the secondary component is selected from the group consisting of methanol, ethanol, isopropanol, n-propanol, tert-butanol, n-butanol, dimethylacetamide, dimethylformamide, N-methylpyrrolidone, methyl ethyl ketone, ethyl acetate, butyl acetate and combinations thereof. In some embodiments, the cleaning solution used in the present method is water. Some non-limiting examples of water include tap water, purified water, pure water, distilled water, deionized water, D20 and combinations thereof. Compared with the use of chemicals for cleaning, the use of water can greatly reduce the harm to the environment and the human body, so the harm to the environment and the human body can be greatly reduced. Secondly, water is an easily accessible resource, economical and affordable, and does not require additional costs. However, some chemical cleaning agents may be expensive and have high usage costs. Finally, using water as the cleaning fluid makes the cleaning process much simpler and does not damage or corrode the electrodes during cleaning. Therefore, using water as the cleaning fluid makes the cleaning process safer and more reliable.
[0063] The cleaning liquid used in the method disclosed in the present invention can be recycled for many times until the cleaning liquid becomes obviously very turbid or the solid-liquid ratio is greater than 30%. The used cleaning liquid can be filtered under pressure or filtered using a filter membrane to obtain black powder. If it is a lithium iron phosphate battery electrode, it includes positive electrode active materials such as lithium iron phosphate, conductive agents such as graphite, etc. The filtered liquid contains a binder, and the aqueous binder can be recovered by a precipitant. Therefore, the materials recovered by the method disclosed in the present invention can be used again to produce batteries. Moreover, after simple filtration, the cleaning liquid can be reused to clean the electrode, thereby reducing waste. If the cleaning liquid is water, even if it is directly discharged after filtration, it will not cause serious pollution to the environment, which is beneficial to environmental protection. Therefore, the method disclosed in the present invention does not require the installation of an additional cleaning liquid treatment system to purify it, saving high equipment purchase and installation costs.
[0064] During the wetting process, various wetting methods can be used, such as spraying or jetting the cleaning liquid to wet the electrode. Wetting the electrode can increase the weight of the electrode, making it close to the conveyor belt, making it easier for the conveyor belt to carry it into the cleaning liquid, so that the electrode does not float to the surface of the cleaning liquid, but is completely immersed in the cleaning liquid. The wetting process using a spray method can also play a role in cleaning the electrode. The sinking of the electrode in the cleaning liquid can avoid the situation where the electrode surface is not fully treated in the subsequent steps.
[0065] Regardless of the wetting method used, the wetting process is completed as long as the electrode is fully wetted. For example, it can also be achieved by spraying the cleaning liquid on the electrode surface or pouring the cleaning liquid from above with a column of water, but it must be ensured that the impact force of the water flow does not cause the electrode to shift or cause the electrode to wrinkle. Other wetting methods can also be used as long as the electrode can be fully wetted. During the wetting process, it is preferred to ensure that the electrode surface is completely wetted.
[0066] In some embodiments, an atomizing nozzle is used to wet the electrode. When using an atomizing nozzle, the cleaning liquid is sprayed out in the form of atomization to form a liquid mist with a very small diameter. The force applied by this spray is small, and when it falls on the surface of the electrode, it will not break the electrode or shift the electrode. While avoiding damage to the electrode, it can also ensure that the position of the electrode on the conveyor belt will not move or shift during the wetting process. In this way, when performing subsequent processes, overlapping of electrodes can be effectively avoided. The use of an atomizing nozzle can basically avoid manual auxiliary processing, which is helpful for subsequent steps.
[0067] In some embodiments, the impact force of the cleaning fluid flow can be controlled by controlling the pressure of the sprayed cleaning fluid, adjusting the aperture of the nozzle, adjusting the height of the cleaning fluid flow, and using a cleaning fluid flow diffuser to avoid electrode displacement or offset and ensure that the electrode is fully wetted.
[0068] In some embodiments, the pressure of the sprayed water can be controlled by adjusting the water pressure of the cleaning liquid, thereby controlling the magnitude of the impact force. The water pressure of the cleaning liquid can also be adjusted by using a regulating valve or a pressure reducer to control the magnitude of the impact force. The water pressure of the sprayed cleaning liquid is usually adjusted within the range of 0.2MPa to 0.5MPa to achieve an appropriate wetting effect while avoiding damage to the electrode.
[0069] In some embodiments, an automatic control system may also be used to monitor and adjust the water pressure of the cleaning fluid to ensure proper spraying intensity and wetting degree.
[0070] In some embodiments, the shape of the nozzle can be circular or elliptical, and the nozzle can be replaced or the aperture size of the nozzle can be adjusted to control the flow rate and impact force of the sprayed cleaning liquid to achieve the desired wetting effect. In some embodiments, the diameter of the nozzle is between 1 mm and 10 mm, between 1 mm and 5 mm, between 1 mm and 4 mm, between 1 mm and 3 mm, or between 1 mm and 2 mm.
[0071] In some embodiments, the impact force of the water flow can be controlled by adjusting the height of the cleaning liquid flow, thereby controlling the wetting degree of the electrode. For the wetting method of spraying the cleaning liquid with a column of water from above, the impact force of the water flow and the wetting degree of the electrode can be controlled by adjusting the height of the cleaning liquid water column falling. Generally, the higher the falling height, the stronger the impact force and the greater the wetting degree. In some embodiments, the height adjustment range of the water column is between 10 cm and 100 cm, between 10 cm and 90 cm, between 10 cm and 80 cm, between 10 cm and 70 cm, between 10 cm and 60 cm, between 10 cm and 50 cm, or between 10 cm and 40 cm, depending on the required impact force and wetting degree. In some embodiments, an automatic control system can be used to monitor and adjust the height and impact force of the cleaning liquid flow.
[0072] In some embodiments, a water diffuser can be used to disperse the cleaning liquid into multiple small water streams, thereby reducing the impact force of a single water stream and achieving a more uniform wetting effect. The water diffuser usually includes a central hole and multiple small holes around it. The cleaning liquid is sprayed out from the central hole and is dispersed into multiple small streams after passing through the diffuser, forming a more uniform wetting effect. The aperture size and number of the water diffuser can be adjusted as needed to achieve the desired wetting effect. Generally, smaller apertures and more small holes can produce weaker impact force and more uniform wetting effect.
[0073] When the binder and electrode active materials on the electrode surface come into contact with the cleaning liquid, the cleaning liquid will penetrate into the electrode layer, initially destroying the ion-dipole interaction and hydrogen bond between the polymer binder and the current collector surface and reducing the interaction between the electrode material and the binder in the electrode layer, making the electrode material on the electrode easier to loosen during the next cleaning step, helping to improve the recycling efficiency.
[0074] The electrode can be operated in the recycling device in different ways, such as a conveyor belt. In some embodiments, the speed of the conveyor belt can be 1 meter to 10 meters per minute to ensure that the electrode layer has enough wetting before entering the next area. In some embodiments, the speed of the conveyor belt can be 1 meter to 9 meters per minute, 1 meter to 8 meters per minute, 1 meter to 7 meters per minute, 1 meter to 6 meters per minute, 1 meter to 5 meters per minute, 1 meter to 4 meters per minute, 1 meter to 3 meters per minute, or 1 meter to 2 meters per minute. In some embodiments, the speed of the conveyor belt can be less than 10 meters per minute, less than 9 meters per minute, less than 8 meters per minute, less than 7 meters per minute, less than 6 meters per minute, less than 5 meters per minute, less than 4 meters per minute, less than 3 meters per minute, or less than 2 meters per minute. In some embodiments, the speed of the conveyor belt can be greater than 9 meters per minute, greater than 8 meters per minute, greater than 7 meters per minute, greater than 6 meters per minute, greater than 5 meters per minute, greater than 4 meters per minute, greater than 3 meters per minute, greater than 2 meters per minute, or greater than 1 meter per minute.
[0075] In addition, a grid can be set on the conveyor belt so that excess cleaning liquid and washed electrode layer materials can be discharged into a collector located below the conveyor belt for further recycling in the system. In order to allow excess cleaning liquid and electrode layer materials to be discharged into the collector below, the grid on the conveyor belt needs to have a sufficient opening area. Generally speaking, the size of the grid should be large enough so that the cleaning liquid and electrode layer materials can flow freely without being blocked, so that the cleaning liquid and electrode layer materials can pass through the grid and be discharged into the collector below. At the same time, it should also be small enough to prevent the electrode from falling into the collector. In some embodiments, the size of the conveyor belt grid for electrode recovery is between a few millimeters and a few centimeters. When the conveyor belt grid size is within this range, the normal operation of the system can be guaranteed, and the efficiency of recycling can be improved.
[0076] In some embodiments, the size of the conveyor belt grid is between 2 mm and 3 cm, between 2 mm and 2.5 cm, between 2 mm and 2 cm, between 2 mm and 1.5 cm, between 2 mm and 1 cm, between 2 mm and 0.5 cm, between 2 mm and 0.25 cm, between 2 mm and 0.1 cm, between 5 mm and 3 cm, between 5 mm and 2.5 cm, between 5 mm and 2 cm, between 5 mm and 1.5 cm, between 5 mm and 1 cm, between 5 mm and 0.5 cm, between 5 mm and 0.25 cm, or between 5 mm and 0.1 cm. The size of the conveyor belt grid can be adjusted according to the amount of cleaning fluid and the specifications of the electrode to ensure that the flow and discharge of the cleaning fluid meet the requirements and that the electrode does not fall. If the cleaning fluid flow is large, a grid with a larger opening area needs to be used to ensure that the cleaning fluid can flow smoothly through the grid and flow into the collector below. If the cleaning fluid flow is small, a grid with a smaller opening area can be used.
[0077] In some embodiments, baffles may be provided on the conveyor belt, and the baffles may be provided at intervals along the direction in which the conveyor belt runs, or the baffles may be provided in a cross manner, so as to fix the position of the electrodes, and to prevent the electrodes from overlapping during the cleaning process, so that some positions cannot be effectively cleaned. In order to adapt to the specifications of different electrodes, the baffles may be provided in a form in which the distance can be adjusted.
[0078] In some embodiments, to prevent the electrode from floating on the surface of the cleaning liquid, the height of the baffle can be set by estimating the buoyancy of the electrode, the baffle can be set in a form that can adjust the height to accommodate electrodes of different specifications, and the water level of the cleaning liquid can be adjusted for electrodes of different specifications by setting scale lines on the baffle. Other similar methods can also be used to achieve the effect of allowing the electrode to sink in the cleaning liquid during ultrasonic cleaning.
[0079] In some embodiments, the temperature of the cleaning solution is about 10°C to about 50°C, and this temperature range can provide sufficient wetting effect without consuming too much energy and cost. Within this temperature range, the cleaning solution can effectively penetrate into the surface and interior of the electrode to remove dirt and impurities, thereby ensuring the cleanliness and performance of the electrode. In some embodiments, the cleaning solution can be used directly at room temperature without additional heating to save energy, reduce costs, and be more environmentally friendly. In other embodiments, the temperature of the cleaning solution is about 10°C to about 50°C, about 20°C to about 40°C, about 20°C to about 30°C, or about 20°C to about 26°C. In some embodiments, the temperature of the cleaning solution is less than 50°C, less than 45°C, less than 40°C, less than 35°C, less than 30°C, or less than 25°C. In some embodiments, the temperature of the cleaning solution is greater than 10°C, greater than 15°C, greater than 20°C, greater than 25°C, greater than 30°C, greater than 35°C, greater than 40°C, or greater than 45°C.
[0080] In some embodiments, in step 102, the electrode is immersed in a cleaning solution and subjected to a first ultrasonic cleaning.
[0081] The conveyor belt moves the electrode from one area to another, and the electrode is sent into the first groove provided with the first ultrasonic generator through the conveyor belt. Once the electrode is immersed in the cleaning solution and ultrasonic cleaning is performed, the binder material of the electrode will be softened and dissolved under the action of ultrasonic waves, thereby separating the current collector and the electrode layer material in the electrode. The electrode layer material in the electrode will be released, and the bond between the current collector and the electrode layer material will also be broken, thereby separating them. This process can effectively improve the recovery rate of the electrode material. If only the room temperature cleaning solution is used to rinse and soak the electrode during the entire process of recycling the electrode without using ultrasonic waves, the dissolution rate of the binder in the electrode will be very slow. This is because the energy of the cleaning solution at room temperature is not enough to destroy and break the ion-dipole interaction and hydrogen bond interaction between the polymer binder and the surface of the current collector. In the absence of ultrasonic waves, the temperature of the cleaning solution may need to be adjusted to 70 to 90°C or higher to dissolve part of the polymer binder. However, in the method disclosed in the present invention, by alternately using the cleaning solution for rinsing and ultrasonic cleaning, the electrode active material and the current collector can be effectively separated even with the cleaning solution at room temperature.
[0082] In some embodiments, an ultrasonic generator may be used in the first ultrasonic cleaning. In some embodiments, different types of ultrasonic generators such as an ultrasonic bath, a probe-type ultrasonic generator, an ultrasonic flow cell, or an ultrasonic vibration plate may be used. In addition, an ultrasonic vibrator may be used to adjust the vibration direction and amount of the ultrasonic wave to control the degree of ultrasonic constructive interference and improve the effect of cleaning the electrode. Different embodiments may use different types of ultrasonic generators to adapt to different electrode materials and cleaning requirements.
[0083] When performing ultrasonic cleaning, the frequency of the ultrasonic generator is crucial. Ultrasonic generators with high frequencies can produce smaller cavitation bubbles, which are suitable for cleaning smaller particles and surfaces. Ultrasonic generators with low frequencies can produce larger cavitation bubbles, which are suitable for cleaning larger particles and surfaces. Since the active material of the electrode completely covers the surface of the current collector and has a large area, it is best to choose a lower frequency ultrasonic generator to clean the electrode during the first ultrasonic cleaning. Although the cavitation bubbles formed at low frequencies are not uniform enough, they close with greater force, which is enough to weaken the ion-dipole interaction and hydrogen bonding between the polymer binder on the electrode and the surface of the current collector, causing the active material to begin to peel off the current collector, making it easier to remove the active material in subsequent steps, achieving a more efficient and comprehensive cleaning effect.
[0084] It should be noted that the time and intensity of ultrasonic cleaning should be adjusted according to the properties of the electrode material and the binder material. If the cleaning time is too short or the intensity is not enough, the binder material may not be completely separated, thus affecting the recovery rate of the electrode layer material and the current collector. In addition, if the cleaning time is too long or the intensity is too high, the current collector itself may also be destroyed or damaged. Therefore, when using ultrasonic cleaning electrodes, appropriate adjustments and controls are required to ensure the best cleaning effect.
[0085] It was found that in the first step, the ultrasonic frequency is preferably in the range of 20kHz and 30kHz, which is very effective for cleaning relatively large active material particles. This result, combined with the subsequent ultrasonic cleaning step, will have an excellent effect. Using low-frequency ultrasound to clean larger active material particles is very effective because low-frequency ultrasound can produce larger cavitation bubbles that can contact larger particles and separate them from the electrode surface. In some embodiments, the frequency of the ultrasonic generator used for the first ultrasonic cleaning is about 20kHz to about 30kHz, about 20kHz to about 25kHz, or about 25kHz to about 30kHz. In some embodiments, the frequency of the ultrasonic generator used for the first ultrasonic cleaning is less than 30kHz, less than 29kHz, less than 28kHz, less than 27kHz, less than 26kHz, less than 25kHz, less than 24kHz, less than 23kHz, less than 22kHz, or less than 21kHz. In some embodiments, the frequency of the ultrasonic generator used for the first ultrasonic cleaning is greater than 20 kHz, greater than 21 kHz, greater than 22 kHz, greater than 23 kHz, greater than 24 kHz, greater than 25 kHz, greater than 26 kHz, greater than 27 kHz, greater than 28 kHz or greater than 29 kHz.
[0086] In some embodiments, ultrasonic generators can be frequency locked, which means that they use a variable controlled by changing the current. In theory, the higher the current, the greater the power and the better the cleaning effect. This can be explained by the following formula: P=VI E∝ω 2 A 2 The power of an ultrasonic generator is proportional to the current. As the input power increases, the ultrasonic energy released also increases. According to the wave equation, the amplitude (A) of the ultrasonic wave increases as the energy (E) increases, and the energy is proportional to the square of the angular frequency (ω).
[0087] It can therefore be inferred that high-amplitude ultrasound waves will cause significant forward radiation when propagating in the cleaning liquid, causing the liquid to flow. This flow will lead to the formation of thousands of tiny bubbles with diameters between 50μm and 500μm, which vibrate violently under the influence of the sound field. These bubbles grow in the negative pressure area where the ultrasound waves propagate longitudinally, and expand rapidly and suddenly collapse in the positive pressure area, generating shock waves and thousands of atmospheres of pressure around them. It should be noted that if the amplitude of the ultrasound waves is too high, huge, high-energy bubbles may be generated, resulting in huge shock waves capable of breaking metal electrodes. Therefore, when powering the ultrasonic generator, care must be taken to control the current to ensure operation at the critical current.
[0088] Figure 4 The double-sided coated cathode in Comparative Example 13 is described as a current collector recovered after cleaning with a cleaning solution and ultrasonic cleaning. During ultrasonic cleaning, the current used by the ultrasonic generator is 6 amperes. It can be observed that the edge of the current collector is uneven, which means that the current of the ultrasonic generator is too large, causing the fragile position of the edge of the current collector to be unable to withstand excessive energy and break, thereby reducing the recovery rate.
[0089] Therefore, the current value of the ultrasonic generator should be adjusted according to the specific cleaning requirements to obtain the best cleaning effect. The current used by the ultrasonic generator for the first ultrasonic cleaning is about 2A to about 5A. In certain embodiments, the current used by the ultrasonic generator for the first ultrasonic cleaning is about 2A to about 4.5A, about 2A to about 4A, about 2A to about 3.5A, about 2A to about 3A, about 2A to about 2.5A, about 2.5A to about 5A, about 2.5A to about 4.5A, about 2.5A to about 4A, about 2.5A to about 3.5A, about 2.5A to about 3A, about 3A to about 5A, about 3A to about 4.5A, about 3A to about 4A, about 3A to about 3.5A, about 3.5A to about 5A, about 3.5A to about 4.5A, about 3.5A to about 4A, about 4A to about 5A, about 4A to about 4.5A or about 4.5A to about 5A.
[0090] In some embodiments, the current used by the ultrasonic generator for the first ultrasonic cleaning is less than 5 A, less than 4.5 A, less than 4 A, less than 3.5 A, less than 3 A, or less than 2.5 A. In some embodiments, the current used by the ultrasonic generator for the first ultrasonic cleaning is greater than 2 A, greater than 2.5 A, greater than 3 A, greater than 3.5 A, greater than 4 A, or greater than 4.5 A.
[0091] The time for immersing the electrode in the cleaning solution for ultrasonic cleaning is critical to achieving complete stripping of the electrode active material from the metal current collector. When the electrode is not cleaned with ultrasound for an adequate time, the aqueous solvent contained in the cleaning solution may not have enough time to shake, disturb and break the ion-dipole interactions and hydrogen bonds initially formed between the coating and the surface of the metal current collector to achieve complete stripping of the electrode active material. However, when the electrode is cleaned with ultrasound for a long time, the metal current collector will corrode due to the prolonged contact time with the cleaning solution. Therefore, it is necessary to control the ultrasonic cleaning time according to the characteristics of the electrode material to obtain the best cleaning effect and avoid potential metal corrosion problems.
[0092] In some embodiments, the time for immersing the electrode in the cleaning solution to receive the first ultrasonic cleaning is preferably about 20 seconds to about 40 seconds. In some embodiments, the time for the first ultrasonic cleaning is about 20 seconds to about 35 seconds, about 20 seconds to about 30 seconds, about 20 seconds to about 25 seconds, about 25 seconds to about 40 seconds, about 25 seconds to about 35 seconds, about 25 seconds to about 30 seconds, about 30 seconds to about 40 seconds, about 30 seconds to about 35 seconds or about 35 seconds to about 40 seconds. In some embodiments, the time for immersing the electrode in the cleaning solution to receive the first ultrasonic cleaning is less than 40 seconds, less than 35 seconds, less than 30 seconds, less than 25 seconds or less than 20 seconds. In some embodiments, the time for immersing the electrode in the cleaning solution to receive the first ultrasonic cleaning is more than 20 seconds, more than 25 seconds, more than 30 seconds or more than 35 seconds.
[0093] In this process, the time for ultrasonic cleaning of the electrode can be controlled by adjusting the speed of the conveyor belt to improve the efficiency of recycling. When using the first ultrasonic cleaning, the speed of the conveyor belt can be the speed when the electrode is wetted.
[0094] Generally speaking, the higher the temperature of the cleaning solution, the better the effect of dissolving the binder. However, it has been found through experiments that when the temperature of the cleaning solution is raised to above room temperature and used to rinse and ultrasonically clean the electrode, the separation effect of the electrode active material and the current collector does not become better. On the contrary, as the temperature of the cleaning solution rises, more electrode materials will remain on the current collector. This is because the temperature of the cleaning solution affects the cavitation phenomenon caused by ultrasound. As the temperature of the cleaning solution rises, the surface tension of the liquid decreases, making the cavitation bubbles therein easier to close. When they close, the maximum temperature and maximum pressure are not reached, thereby reducing the cavitation intensity and the impact force of the cavitation bubbles, and weakening the cleaning effect. In some embodiments, when the first ultrasonic cleaning is performed, the temperature of the cleaning solution in which the electrode is immersed is room temperature. In some embodiments, when the first ultrasonic cleaning is performed, the temperature of the cleaning solution in which the electrode is immersed is about 10°C to about 50°C.
[0095] After the first ultrasonic cleaning is completed, the electrode will be sent away from the first ultrasonic cleaning device by the conveyor belt for the next step of processing. A higher power water pressure nozzle can be used to rinse the electrode layer instead of just spraying.
[0096] In some embodiments, in step 103, the electrode that has undergone the first ultrasonic treatment will be sprayed with a cleaning liquid by hydraulic pressure to remove the electrode layer on the current collector.
[0097] In some embodiments, the nozzle used for the first rinse is a shower nozzle. The use of a shower nozzle can expand the spray range of the cleaning liquid, so that the cleaning liquid evenly covers the electrode, achieving a comprehensive cleaning effect. Preferably, the cleaning liquid sprayed by the shower nozzle for the first rinse has greater force than the cleaning liquid sprayed by the atomizing nozzle used for wetting. After the electrode is ultrasonically cleaned, although the active material is separated from the current collector, some of it will still adhere to the surface of the current collector. Using a stronger water pressure can give the sprayed liquid enough force to wash away the active materials on the surface of the current collector, thereby achieving a more thorough cleaning effect. In addition, when using a nozzle to spray the cleaning liquid, it is necessary to be careful not to damage the electrode due to excessive water pressure. There is no special restriction on the number of nozzles used, but the sprayed cleaning liquid should be able to evenly cover the electrode surface to effectively remove the electrode layer on the surface of the current collector of the electrode.
[0098] Water jetting can also control the impact force by controlling the jet height, thereby effectively removing the coating on the surface of the electrode collector. When the water jet is sprayed from a certain height onto the surface of the electrode collector, a certain impact force will be generated, which can peel the coating off the surface of the collector. By controlling the jet height, the magnitude of the impact force can be adjusted to meet different process requirements.
[0099] The nozzle is arranged perpendicular to the conveyor belt. In some embodiments, the impact force can be controlled by adjusting the angle of the nozzle. The angle of the nozzle arranged below the conveyor belt is preferably inclined along the direction of travel of the conveyor belt, and the inclination angle is in the range of 5 to 45 degrees. This arrangement is very effective for cleaning the electrode close to the conveyor belt, and can effectively reduce the situation where the electrode becomes wrinkled due to the impact force. In some embodiments, the tilt angle of the showerhead is about 5 degrees to about 40 degrees, about 5 degrees to about 30 degrees, about 5 degrees to about 20 degrees, about 5 degrees to about 10 degrees, about 10 degrees to about 40 degrees, about 10 degrees to about 30 degrees, about 10 degrees to about 15 degrees, about 15 degrees to about 40 degrees, about 15 degrees to about 30 degrees, about 15 degrees to about 20 degrees, about 20 degrees to about 40 degrees, about 20 degrees to about 25 degrees, about 25 degrees to about 40 degrees, about 25 degrees to about 30 degrees, about 30 degrees to about 40 degrees, about 30 degrees to about 35 degrees, about 35 degrees to about 40 degrees, or about 40 degrees to about 45 degrees. In some embodiments, the tilt angle of the showerhead is less than 45 degrees, less than 40 degrees, less than 35 degrees, less than 30 degrees, less than 25 degrees, less than 20 degrees, less than 15 degrees, or less than 10 degrees. In some embodiments, the inclination angle of the spray head is greater than 5 degrees, greater than 10 degrees, greater than 15 degrees, greater than 20 degrees, greater than 25 degrees, greater than 30 degrees, greater than 35 degrees, or greater than 40 degrees.
[0100] The study found that using only one ultrasonic treatment method is not enough to completely remove the electrode coating. Although subsequent cleaning can help remove part of the coating, some coating will still remain on the surface of the electrode current collector. Therefore, a second ultrasonic treatment is required to further remove the residual coating. This method can improve the efficiency of removing the coating, and this gentle recycling process will not damage the electrode material, so the performance of the electrode material itself is basically unaffected. The electrode material after cleaning and recycling can be directly used to synthesize new electrodes without further chemical treatment. Batteries prepared using recycled electrode materials are comparable in chemical properties to batteries prepared using new materials. Therefore, the method of recycling electrode materials can effectively reduce waste in the battery production process, and while significantly reducing material waste, it also reduces production costs.
[0101] In some embodiments, in step 104, the electrode is immersed in a cleaning solution and subjected to a second ultrasonic cleaning.
[0102] In some embodiments, the ultrasonic generator used in the second ultrasonic cleaning is the same as that used in the first ultrasonic cleaning. In some embodiments, the ultrasonic generator used in the second ultrasonic cleaning is different from that used in the first ultrasonic cleaning.
[0103] Generally speaking, when using ultrasonic cleaning, increasing the power of the ultrasonic generator can increase the energy of the ultrasonic wave, thereby enhancing the cleaning effect. However, if the particles to be removed are small, even if the power is continuously increased, effective cleaning cannot be achieved. This is because the cavitation bubbles generated at low frequencies are large but few in number, making it difficult for them to contact the small particles, and therefore they cannot be completely removed. This problem can be solved by increasing the frequency of the ultrasonic wave. When the ultrasonic frequency increases, the cavitation bubbles generated are small but more in number, making it easy for them to contact the smaller active material particles and separate them from the electrode surface. This also means that cleaning with only a single frequency cannot remove all active materials. Only low-frequency ultrasonic waves can remove only large and stubborn particles, and only high-frequency ultrasonic waves can clean only finer particles. Therefore, a two-stage ultrasonic cleaning is required, first using low-frequency ultrasonic cleaning, and then using high-frequency ultrasonic cleaning. Since the large active material particles on the electrode surface have been removed after the electrode has been wetting, the first ultrasonic cleaning, and the first rinsing, only some fine active material particles remain attached to the electrode surface. Therefore, compared with the first ultrasonic cleaning, a high frequency is used in the second ultrasonic cleaning to completely remove the small particles and achieve a better cleaning effect.
[0104] It is very important to use two different frequencies of ultrasonic waves for cleaning because it can effectively remove active material particles of different sizes, thereby achieving better cleaning effects. In some embodiments, the frequency of the ultrasonic generator used for the second ultrasonic cleaning is about 35kHz to about 45kHz, about 35kHz to about 40kHz, or about 40kHz to about 45kHz. In some embodiments, the frequency of the ultrasonic generator used for the second ultrasonic cleaning is less than 45kHz, less than 44kHz, less than 43kHz, less than 42kHz, less than 41kHz, less than 40kHz, less than 39kHz, less than 38kHz, less than 37kHz, or less than 36kHz. In some embodiments, the frequency of the ultrasonic generator used for the second ultrasonic cleaning is greater than 35kHz, greater than 36kHz, greater than 37kHz, greater than 38kHz, greater than 39kHz, greater than 40kHz, greater than 41kHz, greater than 42kHz, greater than 43kHz, or greater than 44kHz. Use high-frequency ultrasonic waves for the second cleaning to remove smaller particles, thereby further improving the cleaning effect.
[0105] Figure 3 The current collector recovered after cleaning with a cleaning solution and a single frequency ultrasonic cleaning of the double-sided coated cathode in Comparative Example 1 is described, using 20°C circulating water as the cleaning solution and only one ultrasonic cleaning. However, it can still be observed that the electrode material is firmly adhered to the current collector, which indicates that effective electrode recovery cannot be achieved using only a single frequency ultrasonic cleaning.
[0106] In the second ultrasonic cleaning, the current used can be the same as or smaller than that used in the first ultrasonic cleaning. If a higher frequency ultrasonic wave is used for the second cleaning, a good cleaning effect can be achieved even with a smaller current.
[0107] Since most of the electrode material and other electrode materials have been removed in the first ultrasonic cleaning, the time allowed for the electrode to stay in the ultrasonic cleaning tank in the second ultrasonic cleaning can be the same as or shorter than that in the first ultrasonic cleaning. This is because only smaller particles need to be removed in the second ultrasonic cleaning, and the cleaning time required is shorter than that in the first ultrasonic cleaning. If the second ultrasonic cleaning cleaning time is too long, the electrode current collector may be damaged or over-cleaned. In some embodiments, the time for immersing the electrode in the cleaning solution for the second ultrasonic cleaning is about 20 seconds to about 25 seconds, about 20 seconds to about 24 seconds, about 20 seconds to about 23 seconds, about 21 seconds to about 25 seconds, about 21 seconds to about 24 or about 22 seconds to about 25 seconds. In some embodiments, the time for immersing the electrode in the cleaning solution for the second ultrasonic cleaning is less than 25 seconds, less than 24 seconds, less than 23 seconds, less than 22 seconds or less than 21 seconds. In some embodiments, the time for immersing the electrode in the cleaning solution for the second ultrasonic cleaning is more than 20 seconds, more than 21 seconds, more than 22 seconds, more than 23 seconds or more than 24 seconds.
[0108] In some embodiments, in step 105, the electrode is taken out and rinsed a second time with a cleaning solution. After rinsing the electrode for the second time, it is found that the surface of the electrode current collector is very clean without any cathode material attached to it. This shows that using a water pressure jet method to clean the electrode is a very effective method. In some embodiments, the second rinsing method of the electrode is the same as the first rinsing method. In some embodiments, the second rinsing method of the electrode is different from the first rinsing method.
[0109] In the method disclosed in the present invention, when the electrode is undergoing the de-layering process, the electrode will basically not move or change position, thus avoiding the influence of electrode overlap on the de-layering efficiency. Although, in the process of removing the electrode layer, ultrasonic cleaning and water pressure jetting methods for cleaning the electrode may exert a large force on the electrode, thereby causing the electrode to move or change position, resulting in electrode overlap and affecting the de-layering efficiency, the method disclosed in the present invention will not exert too much force on the electrode. Even if a large force is exerted, the electrode pieces can be separated by a baffle to maintain a relatively stable position, thereby avoiding the problem of electrode overlap and ensuring the stability and reliability of the de-layering efficiency. This result is very important because maintaining the stability and position of the electrode is critical for efficient de-layering. The method disclosed in the present invention can effectively solve this problem and provide a more reliable solution for the de-layering process.
[0110] In some embodiments, the method disclosed in the present invention may further include the step 106 of blowing the cleaned current collector dry. Studies have found that some electrode materials may still be loosely attached to the surface of the current collector and can be removed by mechanical methods such as gently wiping the surface of the current collector. Therefore, the drying can introduce a cleaning method at room temperature and low wind speed to clean the surface of the electrode current collector and remove the loosely attached materials from the surface. In order to blow the electrode material floating on the surface away from the current collector without damaging the electrode, the wind speed of the drying device can be adjusted within the range of 13km / h to 30km / h. The room temperature wind can prevent the metal from deforming due to thermal expansion and contraction, and slow down the rate of metal oxidation. This method can effectively remove the loosely attached materials on the surface, thereby ensuring the cleanliness of the electrode current collector.
[0111] Figure 2 The double-sided coated cathode in Comparative Example 1 is described as being washed with a cleaning solution and cleaned with an ultrasonic wave after recovery of the current collector. The observation results show that no active material remains on the recovered current collector, and the current collector surface is smooth, the edge is flat, and there is no damage. This proves that the present invention is excellent in terms of cleaning effect.
[0112] The electrode is usually composed of an electrode current collector and an electrode layer coated on one or both sides thereof, wherein the electrode layer usually contains a binder, an active material and a conductive agent. The method disclosed in the present invention is suitable for recycling electrodes of secondary batteries. It is particularly important to select a suitable binder when making the cathode electrode, because the binder composed of different types of monomers and the proportion of each monomer not only significantly affects the performance of the battery, but also affects the solubility of the binder during the recycling process. Different types of binders have different chemical and physical properties, such as strength, viscosity and chemical stability. These properties directly affect the uniformity, stability and conductivity of the electrode layer, thereby affecting the performance and life of the battery. The selection of a suitable binder can improve the performance and reliability of the battery, and can also promote the recycling and reuse of the battery.
[0113] In some embodiments, the polymer binder is an aqueous binder, which includes a copolymer and a dispersion medium, wherein the copolymer includes structural unit (a), structural unit (b) and structural unit (c). Each component of the binder and its composition and proportion are very important. The present invention finds that the use of a binder of a specific composition can improve the performance and life of the battery, and can also promote the recycling and reuse of the battery. The binder of this specific composition has high chemical and physical stability, which can ensure the uniformity and stability of the electrode layer, thereby improving the energy density and cycle life of the battery. The specific binder composition can also promote the separation and reuse of electrode materials in the recycling process. Therefore, the content and proportion of the binder need to be carefully controlled during the electrode preparation process to ensure that the electrode has good performance and recyclability.
[0114] The structural unit (a) is derived from a monomer containing an acid group. In some embodiments, the acid group is selected from the group consisting of carboxylic acid, sulfonic acid, sulfuric acid, phosphonic acid, phosphoric acid, nitric acid and combinations thereof. The acids listed above also include their salts and derivatives.
[0115] In some embodiments, the carboxylic acid is acrylic acid, methacrylic acid, crotonic acid, 2-butyl crotonic acid, cinnamic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, 4,4-dimethyl itaconic acid (tetraconic acid) or a combination thereof. In certain embodiments, the carboxylic acid is 2-ethylacrylic acid, isocrotonic acid, cis-2-pentenoic acid, trans-2-pentenoic acid, angelic acid, tiglic acid (tiglic acid) acid), 3,3-dimethylacrylic acid, 3-propylacrylic acid, trans-2-methyl-3-ethylacrylic acid, cis-2-methyl-3-ethylacrylic acid, 3-isopropylacrylic acid, trans-3-methyl-3-ethylacrylic acid, cis-3-methyl-3-ethylacrylic acid, 2-isopropylacrylic acid, trimethylacrylic acid, 2-methyl-3,3-diethylacrylic acid, 3-butylacrylic acid, 2-butylacrylic acid, 2-pentylacrylic acid, 2-methyl-2-hexenoic acid, trans-3-methyl-2-hexenoic acid, 3-methyl-3-propylacrylic acid, 2-ethyl-3-propylacrylic acid, 2,3-diethylacrylic acid, 3,3-diethylacrylic acid, 3-methyl-3-hexylacrylic acid, 3-methyl-3-tert-butylacrylic acid, 2-methyl-3-pentylacrylic acid, 3-methyl-3-pentylacrylic acid, 4-methyl-2-hexenoic acid, 4-ethyl-2-hexenoic acid, 3-methyl-2-ethyl-2-hexenoic acid, 3-tert-butylacrylic acid, 2,3-dimethyl-3-ethylacrylic acid, 3,3-dimethyl-2-ethylacrylic acid, 3-methyl-3-isopropylacrylic acid, 2-methyl-3-isopropylacrylic acid, trans-2-octenoic acid, cis-2-octenoic acid, trans-2-decenoic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid or a combination thereof.
[0116] In some embodiments, the carboxylic acid is methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, bromomaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, difluoromaleic acid, nonyl hydrogen maleate, decyl hydrogen maleate, dodecyl hydrogen maleate, octadecyl hydrogen maleate, fluoroalkyl hydrogen maleate, or a combination thereof. In some embodiments, the carboxylic acid is maleic anhydride, methylmaleic anhydride, dimethylmaleic anhydride, acrylic anhydride, methacrylic anhydride, methacrolein, methacryloyl chloride, methacryloyl fluoride, methacryloyl bromide, or a combination thereof.
[0117] In some embodiments, the sulfonic acid is vinyl sulfonic acid, methyl vinyl sulfonic acid, allyl vinyl sulfonic acid, allyl sulfonic acid, methyl allyl sulfonic acid, styrene sulfonic acid, 2-sulfoethyl methacrylic acid, 2-methyl-2-propylene-1-sulfonic acid, 2-acrylamido-2-methyl-1-propane sulfonic acid, 3-allyloxy-2-hydroxy-1-propane sulfonic acid, or a combination thereof.
[0118] In some embodiments, the sulfuric acid is allyl hydrogen sulfate, vinyl hydrogen sulfate, 4-allylphenol sulfate, or a combination thereof.
[0119] In some embodiments, the phosphonic acid is vinylphosphonic acid, allylphosphonic acid, vinylbenzylphosphonic acid, acrylamidoalkylphosphonic acid, methacrylamidoalkylphosphonic acid, acrylamidoalkyldiphosphonic acid, acrylphosphonic acid, 2-methacryloyloxyethylphosphonic acid, bis(2-methacryloyloxyethyl)phosphonic acid, ethylene 2-methacryloyloxyethylphosphonic acid, ethyl-methacryloyloxyethylphosphonic acid, or a combination thereof.
[0120] In some embodiments, the phosphoric acid is mono(2-acryloyloxyethyl)phosphate, mono(2-methacryloyloxyethyl)phosphate, diphenyl(2-acryloyloxyethyl)phosphate, diphenyl(2-methacryloyloxyethyl)phosphate, phenyl(2-acryloyloxyethyl)phosphate, methacrylate phosphoryloxyethyl, methacrylate-3-chloro-2-phosphoryloxypropyl, monomethacrylate phosphoryloxypoly(ethylene glycol), methacrylate phosphoryloxypoly(propylene glycol), (meth)acryloyloxyethyl phosphoric acid. Ester, (meth)acryloxypropyl phosphate, (meth)acryloxy-2-hydroxypropyl phosphate, (meth)acryloxy-3-hydroxypropyl phosphate, (meth)acryloxy-3-chloro-2-hydroxypropyl phosphate, allyl hydrogen phosphate, vinyl hydrogen phosphate, allyl hydrogen pyrophosphate, vinyl hydrogen pyrophosphate, allyl hydrogen tripolyphosphate, vinyl hydrogen tripolyphosphate, allyl hydrogen tetrapolyphosphate, vinyl hydrogen tetrapolyphosphate, allyl hydrogen trimetaphosphate, vinyl hydrogen trimetaphosphate, isopentenyl phosphate, isopentenyl pyrophosphate, or a combination thereof.
[0121] In some embodiments, the nitric acid is allyl hydrogen nitrate, ethylene hydrogen nitrate, or a combination thereof.
[0122] In some embodiments, based on the total moles of monomer units in the copolymer in the binder composition, the proportion of structural unit (a) in the copolymer is about 15% to about 50%, about 15% to about 48%, about 15% to about 45%, about 15% to about 42%, about 15% to about 40%, about 15% to about 38%, about 15% to about 35%, about 15% to about 32%, about 15% to about 30%, about 15% to about 28%, about 15% to about 25%, about 20% to about 50%, about 20% to about 48%, about 20% to about 50%, about 20% to about 48%, about 20% to about 42%, about 15% to about 40%, about 15% to about 38%, about 15% to about 35%, about 15% to about 32%, about 15% to about 30%, about 15% to about 28%, about 15% to about 25 ... From about 25% to about 40%, from about 25% to about 38%, from about 20% to about 35%, from about 20% to about 32%, from about 20% to about 30%, from about 25% to about 50%, from about 25% to about 48%, from about 25% to about 45%, from about 25% to about 42%, from about 25% to about 40%, from about 25% to about 38%, from about 25% to about 35%, from about 30% to about 50%, from about 30% to about 48%, from about 30% to about 45%, from about 25% to about 42%, from about 25% to about 40%, from about 25% to about 38%, from about 25% to about 35%, from about 30% to about 50%, from about 30% to about 48%, from about 30% to about 45%, from about 30% to about 42%, or from about 30% to about 40%.
[0123] In some embodiments, based on the total moles of monomer units in the copolymer in the binder composition, the proportion of structural unit (a) in the copolymer is less than 50%, less than 48%, less than 45%, less than 42%, less than 40%, less than 38%, less than 35%, less than 32%, less than 30%, less than 28%, less than 25%, less than 22%, less than 20% or less than 18% by mole. In some embodiments, based on the total moles of monomer units in the copolymer in the binder composition, the proportion of structural unit (a) in the copolymer is more than 15%, more than 18%, more than 20%, more than 22%, more than 25%, more than 28%, more than 30%, more than 32%, more than 35%, more than 38%, more than 40%, more than 42%, more than 45% or more than 48% by mole.
[0124] The structural unit (b) is derived from a monomer selected from the group consisting of an amide group-containing monomer, a hydroxyl group-containing monomer, and a combination thereof.
[0125] In some embodiments, the monomer containing an amide group is acrylamide, methacrylamide, N-methyl methacrylamide, N-ethyl methacrylamide, N-n-propyl methacrylamide, N-isopropyl methacrylamide, isopropyl acrylamide, N-n-butyl methacrylamide, N-isobutyl methacrylamide, N,N-dimethyl acrylamide, N,N-dimethyl methacrylamide, N,N-diethyl acrylamide, N,N-diethyl methacrylamide, N-hydroxymethyl methacrylamide, N-(methoxymethyl) methacrylamide, N-(ethoxymethyl) methacrylamide, 1-(4-(6-methyl)methacrylamide, N-(2-(4-methyl)methacrylamide, N-(3-(dimethylamino)propyl)methacrylamide, N-(2-(dimethylamino)ethyl)methacrylamide, N,N-(dihydroxymethyl)methacrylamide, diacetone methacrylamide, diacetone acrylamide, methacryl morpholine, N-hydroxymethylacrylamide, N-methoxymethylacrylamide, N-methoxymethylmethacrylamide, N,N'-methylenebisacrylamide (MBA), N-hydroxymethylacrylamide, or a combination thereof.
[0126] In some embodiments, the hydroxyl group-containing monomer is a hydroxyl group-containing monomer having a C1 to C 20 Alkyl group or C5 to C 20In some embodiments, the monomer containing a hydroxyl group is 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 5-hydroxypentyl acrylate, 6-hydroxyhexyl methacrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, 3-chloro-2-hydroxypropyl methacrylate, diethylene glycol mono(meth)acrylate, allyl alcohol, or a combination thereof.
[0127] In some embodiments, based on the total moles of monomer units in the copolymer in the binder composition, the proportion of the structural unit (b) in the copolymer is about 4% to about 25%, about 4% to about 24%, about 4% to about 23%, about 4% to about 22%, about 4% to about 21%, about 4% to about 20%, about 4% to about 19%, about 4% to about 18%, about 4% to about 17%, about 4% to about 16%, about 4% to about 15%, about 4% to about 14%, about 4% to about 13%, about 7% to about 25%, about 7% to about 24%, about 7% to about 23%, about 7% to about 22%, about 7% to about 21%, about 7% to about 20%, about 7% to about 19%, about 7% to about 18%, about 7% to about 17%, about 7% to about 18%, about 7% to about 19%, about 7% to about 18%, about 7% to about 17%, about 7% to about 19%, about 7% to about 18 ... %, about 7% to about 16%, about 7% to about 15%, about 10% to about 25%, about 10% to about 24%, about 10% to about 23%, about 10% to about 22%, about 10% to about 21%, about 10% to about 20%, about 10% to about 19%, about 10% to about 18%, about 10% to about 17%, about 10% to about 16%, about 10% to about 15%, about 13% to about 25%, about 13% to about 24%, about 13% to about 23%, about 13% to about 22%, about 13% to about 21%, about 13% to about 20%, about 15% to about 25%, about 15% to about 24%, about 15% to about 23%, about 15% to about 22%, about 15% to about 21%, or about 15% to about 20%.
[0128] In some embodiments, based on the total moles of monomer units in the copolymer in the binder composition, the proportion of structural unit (b) in the copolymer is less than 25%, less than 24%, less than 23%, less than 22%, less than 21%, less than 20%, less than 19%, less than 18%, less than 17%, less than 16%, less than 15%, less than 14%, less than 13%, less than 12%, less than 11%, less than 10%, less than 9%, less than 8%, less than 7%, less than 6% or less than 5% by mole. In some embodiments, based on the total moles of monomer units in the copolymer in the binder composition, the proportion of structural unit (b) in the copolymer is more than 4%, more than 5%, more than 6%, more than 7%, more than 8%, more than 9%, more than 10%, more than 11%, more than 12%, more than 13%, more than 14%, more than 15%, more than 16%, more than 17%, more than 18%, more than 19%, more than 20%, more than 21%, more than 22%, more than 23% or more than 24% by mole.
[0129] The structural unit (c) is derived from a monomer selected from the group consisting of a nitrile group-containing monomer, an ether group-containing monomer, an epoxy group-containing monomer, a carbonyl group-containing monomer, a fluorine-containing monomer, and a combination thereof.
[0130] In some embodiments, the monomer containing nitrile groups includes α, β-ethylenically unsaturated nitrile monomers. In some embodiments, the monomer containing nitrile groups is acrylonitrile, α-haloacrylonitrile, α-alkylacrylonitrile or a combination thereof. In some embodiments, the monomer containing nitrile groups is α-chloroacrylonitrile, α-bromoacrylonitrile, α-fluoroacrylonitrile, methacrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, α-n-hexylacrylonitrile, α-methoxyacrylonitrile, 3-methoxyacrylonitrile, 3-ethoxyacrylonitrile, α-acetoxyacrylonitrile, α-phenylacrylonitrile, α-tolylacrylonitrile, α-(methoxyphenyl)acrylonitrile, α-(chlorophenyl)acrylonitrile, α-(cyanophenyl)acrylonitrile, vinylidene cyanide or a combination thereof.
[0131] In some embodiments, the ether group-containing monomer is vinyl ether, allyl ether, allyl vinyl ether, allyl glycidyl ether, 2H-hexafluoroisopropyl allyl ether, hydroxypolyethoxy (10) allyl ether, allyl phenyl ethyl ether, ethyl vinyl ether, propyl vinyl ether, n-butyl vinyl ether, or a combination thereof.
[0132] In some embodiments, the epoxy group-containing monomer is vinyl glycidyl ether, allyl glycidyl ether, allyl-2,3-epoxypropyl ether, butenyl glycidyl ether, butadiene monoepoxide, chloroprene monoepoxide, 3,4-epoxy-1-butene, 4,5-epoxy-2-pentene, 3,4-epoxy-1-vinylcyclohexane, 1,2-epoxy-4-vinylcyclohexane, 3,4-epoxycyclohexylethylene, epoxy-4-vinylcyclohexene, 1,2-epoxy-5,9-cyclododecadiene, or a combination thereof. In some embodiments, the epoxy group-containing monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-9-decene, glycidyl acrylate, glycidyl methacrylate, glycidyl crotonate, glycidyl 2,4-dimethylpentenoate, glycidyl 4-hexenoate, glycidyl 4-hexenoate, glycidyl 5-methyl-4-hexenoate, glycidyl sorbate, glycidyl linoleate, glycidyl oleate, glycidyl 3-butenoate, glycidyl 3-pentenoate, glycidyl 4-methyl-3-pentenoate, or a combination thereof.
[0133] In some embodiments, the monomer containing a carbonyl group is methyl vinyl ketone, ethyl vinyl ketone, acrolein, acryloyl chloride, cinnamaldehyde, E-crotonaldehyde, 2-hexenal, 2-octenal, 2-methyl-2-pentenal, 4-methyl-3-penten-2-one, 1-octen-3-one, 2-pentyl-1-butene-3-one, or a combination thereof.
[0134] In some embodiments, the fluorinated monomer is a C1-C 20 Acrylate or methacrylate or a combination thereof containing an alkyl group, wherein the monomer contains at least one fluorine atom. In some embodiments, the fluorine-containing monomer is a perfluoroalkyl acrylate, such as perfluorododecyl acrylate, perfluoro-n-octyl acrylate, perfluoro-n-butyl acrylate, perfluorohexylethyl acrylate, and perfluorooctylethyl acrylate; a perfluoroalkyl methacrylate, such as perfluorododecyl methacrylate, perfluoro-n-octyl methacrylate, perfluoro-n-butyl methacrylate, perfluorohexylethyl methacrylate, and perfluorooctylethyl methacrylate; a perfluorooxyalkyl acrylate, such as perfluorododecyloxyethyl acrylate and perfluorodecyloxyethyl acrylate; a perfluorooxyalkyl methacrylate, such as perfluorododecyloxyethyl methacrylate and perfluorodecyloxyethyl methacrylate, or a combination thereof. In some embodiments, the fluorine-containing monomer is a C1-C 20A carboxylate salt of an alkyl group and at least one fluorine atom, wherein the carboxylate salt is selected from the group consisting of crotonate, malate, fumarate, itaconate or a combination thereof. In some embodiments, the fluorine-containing monomer is vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene, fluoroalkyl vinyl ether, perfluoroalkyl vinyl ether, hexafluoropropylene, 2,3,3,3-tetrafluoropropylene, vinylidene fluoride, tetrafluoroethylene, 2-fluoroacrylate or a combination thereof.
[0135] In some embodiments, based on the total moles of monomer units in the copolymer in the binder composition, the proportion of structural unit (c) in the copolymer is about 46% to about 65%, about 46% to about 64%, about 46% to about 63%, about 46% to about 62%, about 46% to about 61%, about 46% to about 60%, about 46% to about 59%, about 46% to about 58%, about 46% to about 57%, about 46% to about 56%, about 50% to about 51%, about 52% to about 53%, about 54% to about 55%, about 56% to about 57%, about 58% to about 59%, about 58% to about 51%, about 52% to about 53%, about 54% to about 55%, about 56% to about 56%, about 57 ...6% to about 56%, about 57% to about 56%, about 56% to about 52%, about 56% to about 52%, about 56% to about 53%, about 56% to about 56%, about 56% to about 52%, about 56% to about 52%, about 56% to about 52%, about 51% to about 5 % to about 65%, about 50% to about 64%, about 50% to about 63%, about 50% to about 62%, about 50% to about 61%, about 50% to about 60%, about 50% to about 59%, about 50% to about 58%, about 50% to about 57%, about 50% to about 56%, about 55% to about 65%, about 55% to about 64%, about 55% to about 63%, about 55% to about 62%, about 55% to about 61%, or about 55% to about 60%.
[0136] In some embodiments, based on the total moles of monomer units in the copolymer in the binder composition, the proportion of structural unit (c) in the copolymer is less than 65%, less than 64%, less than 63%, less than 62%, less than 61%, less than 60%, less than 59%, less than 58%, less than 57%, less than 56%, less than 55%, less than 54%, less than 53%, less than 52%, less than 51%, less than 50%, less than 49%, less than 48%, or less than 47% by mole. In some embodiments, based on the total moles of monomer units in the copolymer in the binder composition, the proportion of structural unit (c) in the copolymer is more than 46%, more than 47%, more than 48%, more than 49%, more than 50%, more than 51%, more than 52%, more than 53%, more than 54%, more than 55%, more than 56%, more than 57%, more than 58%, more than 59%, more than 60%, more than 61%, more than 62%, more than 63% or more than 64% by mole.
[0137] The present invention finds that selecting the appropriate composition and ratio of the above structural unit (a), structural unit (b), and structural unit (c) can improve the performance and recyclability of the battery. Therefore, in the design and manufacturing process of the battery, it is necessary to carefully select a suitable binder and optimize its composition and ratio.
[0138] In some embodiments, the electrode active material is a cathode active material, wherein the cathode active material is selected from the group consisting of LiCoO2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, Li2MnO3, LiFeO2, LiFePO4, and combinations thereof. In other embodiments, the cathode active material is not LiCoO2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, LiFeO2, or LiFePO4. In further embodiments, the cathode active material is not LiNi x Mn y O2、Li 1+z Ni x Mn y Co 1-x-y O2 or LiNi x Co y Al z O2, wherein each x is independently 0.2 to 0.9; each y is independently 0.1 to 0.45; and each z is independently 0 to 0.2.
[0139] Since an aqueous binder is used, this recycling method is particularly suitable for recycling batteries manufactured by a water-based method. The presence of nickel metal makes the pH value of the water-based electrode slurry more alkaline, thereby affecting the bonding strength of the electrode layer and the connection with the current collector. The present invention finds that the electrode layer containing nickel metal is generally difficult to recycle and has a low recovery rate. In a further embodiment, the positive electrode material does not contain nickel metal.
[0140] In certain embodiments, the cathode active material is doped with a dopant selected from the group consisting of Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, and combinations thereof. In some embodiments, the dopant is not Fe, Ni, Mn, Mg, Zn, Ti, La, Ce, Ru, Si, or Ge. In certain embodiments, the dopant is not Al, Sn, or Zr.
[0141] In certain embodiments, the cathode active material comprises or is itself a core-shell composite having a core and shell structure, wherein the core comprises a lithium transition metal oxide selected from the group consisting of Li 1+x Ni a Mn b Co c Al (1-a-b-c) O2, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li2MnO3, LiCrO2, Li4Ti5O 12, LiV2O5, LiTiS2, LiMoS2 and combinations thereof, wherein -0.2≤x≤0.2, 0≤a<1, 0≤b<1, 0≤c<1 and a+b+c≤1; wherein the shell comprises a lithium transition metal oxide selected from the group consisting of LiCoO2, LiMnO2, LiMn2O4, Li2MnO3, LiCrO2, Li4Ti5O 12 , LiV2O5, LiTiS2, LiMoS2 and a group consisting of combinations thereof. In other embodiments, the core and the shell each independently comprise two or more lithium transition metal oxides. In some embodiments, one of the core or the shell comprises only one lithium transition metal oxide, and the other comprises two or more lithium transition metal oxides. The lithium transition metal oxides in the core and the shell may be the same or different or partially different. In some embodiments, two or more lithium transition metal oxides are uniformly distributed in the core. In certain embodiments, two or more lithium transition metal oxides are unevenly distributed in the core. In some embodiments, the cathode active material is not a core-shell composite.
[0142] In some embodiments, each of the lithium transition metal oxides in the core and the shell is independently doped with a dopant selected from the group consisting of Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, and combinations thereof. In certain embodiments, the core and the shell each independently comprise two or more doped lithium transition metal oxides. In some embodiments, the two or more doped lithium transition metal oxides are uniformly distributed on the core and / or shell. In certain embodiments, the two or more doped lithium transition metal oxides are unevenly distributed on the core and / or shell.
[0143] In some embodiments, the cathode active material comprises or is itself a core-shell composite, which includes a core comprising a lithium transition metal oxide and a shell comprising a transition metal oxide. In certain embodiments, the lithium transition metal oxide is selected from Li 1+x Ni a Mn b Co c Al (1-a-b-c) O2, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li2MnO3, LiCrO2, Li4Ti5O 12, LiV2O5, LiTiS2, LiMoS2, and combinations thereof; wherein -0.2≤x≤0.2, 0≤a<1, 0≤b<1, 0≤c<1, and a+b+c≤1. In some embodiments, the transition metal oxide is selected from the group consisting of Fe2O3, MnO2, Al2O3, MgO, ZnO, TiO2, La2O3, CeO2, SnO2, ZrO2, RuO2, and combinations thereof. In certain embodiments, the shell comprises a lithium transition metal oxide and a transition metal oxide.
[0144] In some embodiments, the diameter of the core is about 1 μm to about 15 μm, about 3 μm to about 15 μm, about 3 μm to about 10 μm, about 5 μm to about 10 μm, about 5 μm to about 45 μm, about 5 μm to about 35 μm, about 5 μm to about 25 μm, about 10 μm to about 45 μm, about 10 μm to about 40 μm, about 10 μm to about 35 μm, about 10 μm to about 25 μm, about 15 μm to about 45 μm, about 15 μm to about 30 μm, about 15 μm to about 25 μm, about 20 μm to about 35 μm, or about 20 μm to about 30 μm. In certain embodiments, the thickness of the shell is from about 1 μm to about 45 μm, from about 1 μm to about 35 μm, from about 1 μm to about 25 μm, from about 1 μm to about 15 μm, from about 1 μm to about 10 μm, from about 1 μm to about 5 μm, from about 3 μm to about 15 μm, from about 3 μm to about 10 μm, from about 5 μm to about 10 μm, from about 10 μm to about 35 μm, from about 10 μm to about 20 μm, from about 15 μm to about 30 μm, from about 15 μm to about 25 μm, or from about 20 μm to about 35 μm. In certain embodiments, the diameter or thickness ratio of the core to the shell is in the range of 15:85 to 85:15, 25:75 to 75:25, 30:70 to 70:30, or 40:60 to 60:40. In certain embodiments, the volume or weight ratio of core to shell is 95:5, 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, or 30:70.
[0145] The current collector collects electrons generated by the electrochemical reaction of the cathode active material, or provides electrons required for the electrochemical reaction. In some embodiments, the current collector can be in the form of a foil, a sheet, or a film. In some embodiments, the current collector is stainless steel, titanium, nickel, aluminum, copper, or an alloy thereof, or a conductive resin. In some embodiments, the current collector has a two-layer structure including an outer layer and an inner layer, wherein the outer layer includes a conductive material, and the inner layer includes an insulating material or another conductive material; for example, aluminum covered with a conductive resin layer or a polymer insulating material coated with an aluminum film. In some embodiments, the current collector has a three-layer structure, which includes an outer layer, an intermediate layer, and an inner layer, wherein the outer layer and the inner layer include a conductive material, and the intermediate layer includes an insulating material or another conductive material; for example, a plastic substrate coated with a metal film on both sides. In some embodiments, each of the outer layer, the intermediate layer, and the inner layer is independently stainless steel, titanium, nickel, aluminum, copper, or an alloy thereof, or a conductive resin. In some embodiments, the insulating material is a polymer material selected from the group consisting of polycarbonate, polyacrylate, polyacrylonitrile, polyester, polyamide, polystyrene, polyurethane, polyepoxy, poly(acrylonitrile butadiene styrene), polyimide, polyolefin, polyethylene, polypropylene, polyphenylene sulfide, poly(vinyl ester), polyvinyl chloride, polyether, polyphenylene ether, cellulose polymer and combinations thereof. In some embodiments, the current collector has a structure of more than three layers. In some embodiments, the current collector is coated with a protective coating. In some embodiments, the protective coating comprises a carbonaceous material. In some embodiments, the current collector is not coated with a protective coating.
[0146] In certain embodiments, the electrode further comprises a conductive agent. The conductive agent is used to enhance the conductivity of the electrode. Any suitable material can be used as the conductive agent. In some embodiments, the conductive agent is a carbonaceous material. Some non-limiting examples include carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fiber, carbon nanofiber, graphitized carbon sheet, carbon tube, activated carbon, Super P, KS6, vapor grown carbon fiber (VGCF), mesoporous carbon and combinations thereof.
[0147] The method disclosed in the present invention can remove the electrode layer on the surface of the metal material on the positive and negative electrodes by alternately cleaning the electrodes and ultrasonic cleaning, and the recovered current collector and electrode material can be reused in preparing batteries, thus promoting the circular economy. In addition, the used cleaning liquid can be collected and recycled, thereby reducing the waste and pollution of water resources.
[0148] The following examples are provided to illustrate embodiments of the present invention, but are not intended to limit the present invention to the specific embodiments listed. Unless otherwise indicated, all parts and percentages are by weight. All numerical values are approximate. When numerical ranges are given, it should be understood that the embodiments outside the stated range still fall within the scope of the present invention. The specific details described in each embodiment should not be understood as essential features of the present invention. Example
[0149] The recovery rate refers to the ratio of the weight of the current collector after cleaning to the original weight of the current collector. It can be calculated by the formula: Due to the very strict requirements for manufacturing batteries, the thickness and density of the current collector must be uniform, so the weight of the current collector with the same surface area is the same. Through experiments, the current collectors without slurry coating were collected, cut into the same size and weighed, and it was found that there was only a very small error between the weights of each current collector. Therefore, the original weight can be further calculated by measuring the size of the current collector. Example 1 A) Preparation of polymer binder
[0150] 11.90 g of sodium hydroxide (NaOH) was added to a round bottom flask containing 380 g of distilled water. The mixture was stirred at 80 rpm for 30 minutes to obtain a first suspension.
[0151] 24.78 g of acrylic acid was added to the first suspension. The mixture was further stirred at 80 rpm for 30 minutes to obtain a second suspension.
[0152] 7.19 g of acrylamide was dissolved in 10 g of deionized water to form an acrylamide solution. Thereafter, all of the acrylamide solution was added to the second suspension. The mixture was further heated to 55° C. and stirred at 80 rpm for 45 minutes to obtain a third suspension.
[0153] 30.06 g of acrylonitrile was added to the third suspension. The mixture was further stirred at 80 rpm for 10 minutes to obtain a fourth suspension.
[0154] Then, 0.03 g of a water-soluble free radical initiator (ammonium persulfate, APS; from Aladdin Industries, China) was dissolved in 3 g of deionized water, and 0.015 g of a reducing agent (sodium bisulfite; from Tianjin Damao Chemical Reagent Factory, China) was dissolved in 1.5 g of deionized water. All of the APS solution and the sodium bisulfite solution were added to the fourth suspension. The mixture was stirred at 55° C. at a rotation speed of 200 rpm for 24 h to obtain a fifth suspension.
[0155] After the reaction is complete, the temperature of the fifth suspension is lowered to 25° C. 3.72 g of NaOH is dissolved in 400 g of deionized water to form a sodium hydroxide solution. Thereafter, all of the sodium hydroxide solution is added dropwise to the fifth suspension over 1 hour to adjust the pH to 7.3 to form a sixth suspension. The sixth suspension is filtered using a 200 μm nylon mesh to form a polymer binder. B) Preparation of cathode
[0156] 12 g of a conductive agent (Super P; from Timcal Ltd, Bodio, Switzerland) and 100 g of the above synthesized polymer binder were dispersed in 74 g of deionized water and stirred with an overhead stirrer (R20, IKA) to prepare a first mixture. After addition, the first mixture was further stirred at 1,200 rpm for about 30 minutes at 25°C.
[0157] Then, 276 g of LiFePO4 (Tianjin Sitelan Energy Technology Co. Ltd., China) was added to the first mixture while stirring with an overhead stirrer at 25° C. to prepare a second mixture. The second mixture was then degassed at a pressure of about 10 kPa for 1 hour. The second mixture was then further stirred at 1,200 rpm for about 60 minutes at 25° C. to form a homogenized cathode slurry.
[0158] The homogenized cathode slurry was coated on both sides of an aluminum foil with a thickness of 16 μm as a current collector using a blade coater with a gap width of 120 μm. The thickness of each side of the coating slurry was 80 μm, and the coating slurry on both sides of the aluminum foil was dried at 85 ° C using an electric heating oven to form a cathode electrode layer. The drying time was about 120 minutes. The electrode was then pressed to reduce the thickness of the electrode layer on each side of the cathode to 34 μm each. C) Electrode recovery
[0159] The cathode prepared above is recovered using a battery electrode cleaning device. The battery electrode cleaning device comprises a housing, a circulating water tank and a conveying device are arranged in the housing, wherein the circulating water tank contains circulating water at 20°C as a cleaning liquid; and the conveying device comprises a motor, a rotating shaft and a conveying belt.
[0160] Cut the electrode prepared in step B into a size of 185 mm × 125 mm, and place the electrode on the conveyor belt. Multiple electrodes can be placed horizontally and vertically, and the electrodes do not overlap each other. Turn on the power of the device and start the conveyor. The electrode is transported as the conveyor rotates, and is first transported to the bottom of the first spray device, and is wetted with a cleaning liquid. The first spray device uses an atomizing nozzle.
[0161] After the wetting treatment, the electrode enters the first groove and is immersed therein. A first ultrasonic generator is provided in the groove to clean the electrode at a frequency of 28 kHz and a current of 2 A for 40 seconds.
[0162] After cleaning, the electrode continues to move toward the second spray device. The second spray device uses a shower-type nozzle. There are multiple nozzles above the conveyor belt to spray and clean the electrode with water. The nozzle below the conveyor belt is inclined 15 degrees along the direction of the conveyor belt to clean the electrode.
[0163] After the cleaning is completed, the electrode continues to move toward the second ultrasonic generator, enters and immerses in the second groove provided with the second ultrasonic generator. The second ultrasonic generator performs a second cleaning of the metal material at a frequency of 38kHz and a current of 2A. The cleaning time is 25 seconds.
[0164] After cleaning, the electrode continues to move toward the third spray device. The third spray device also uses a shower-type nozzle, and nozzles are provided above and below the conveyor belt. The water pressure for spray cleaning here can be slightly greater than the water pressure of the first spray device and the second spray device.
[0165] During cleaning, the circulating water can be directly observed to determine whether it needs to be replaced, or it can be directly tested using a halogen moisture meter (XY·100MW·A, from Changzhou Lucky Electronic Equipment Co., Ltd.). When the test result is greater than 30%, the circulating water needs to be replaced.
[0166] Finally, the cleaned electrode is transported to the unloading platform to complete the entire cleaning process. The cleaned electrode is blown dry by a blow-drying device with room temperature and low wind speed to obtain a dry current collector. The weight of the current collector is measured, and the recovery rate is calculated and shown in Table 1.
[0167] After the cleaning process is completed, the used cleaning liquid is collected and a suction filter (HNTM-30-1 laboratory ceramic membrane filter from Shaoxing Haina Membrane Technology Co., Ltd.) is used to filter out the electrode materials in the circulating water, the main components of which are lithium iron phosphate and conductive agent.
[0168] The circulating water after suction filtration contains a binder, and the binder disclosed in the specification of the present invention can be removed from the circulating water by adding a sedimentation agent. (1) Step 1: Dissolve 98 g of sulfuric acid in 1 L of distilled water to form a 1 M sulfuric acid solution. (2) Step 2: 1M sulfuric acid solution is added to circulating water to form a suspension with a pH of 4.24. The suspension is stirred at 200 rpm for 10 minutes at 25°C. The binder is then precipitated. After the binder is precipitated, the treated suspension is removed by filter paper to recover the precipitated binder. The recovered binder is dried in an oven at 80°C and atmospheric pressure for 5 hours.
[0169] The cleaning method of the negative electrode is the same as that of the positive electrode. After the negative electrode is cleaned, a suction filter is used to filter out the electrode materials in the circulating water, the main components of which are carbon powder and conductive agent. D) Preparation of soft-pack lithium-ion batteries
[0170] The cathode was prepared by the method described in step B, except that no conductive agent was added, and the same weight of positive electrode material obtained after filtration of the washing liquid was added to the first mixture instead of 276 g LiFePO4.
[0171] 93wt.% of graphite (BTR New Energy Materials Inc., Shenzhen, Guangdong, China) was mixed with 1wt.% of carboxymethyl cellulose (CMC, BSH-12, DKS Co. Ltd., Japan) as a binder and 3wt.% of SBR (AL-2001, NIPPONA & L, Japan) and 3wt.% of carbon black as a conductive agent in deionized water to prepare an anode slurry. The solid content of the anode slurry was 51.5wt.%. The slurry was coated on both sides of a copper foil having a thickness of 8μm using a knife coater with a gap width of about 120μm. The coated slurry on the copper foil was dried at about 85°C for 120 minutes by a hot air dryer to obtain an anode. The electrode was then pressed to reduce the thickness of the anode electrode layer to 60μm, and the surface density of the anode electrode layer was 10mg / cm 2 .
[0172] After drying, the resulting cathode and anode were cut into rectangular sheets of 5.2 cm × 8.5 cm and 5.4 cm × 8.7 cm, respectively. A soft-pack lithium-ion battery was prepared by alternately stacking the cathode and anode and separating them with a porous polyethylene separator (Celgard, LLC, USA) with a thickness of 25 μm. The electrolyte was a solution containing LiPF6 (1 M) in a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1. The battery was assembled in a high-purity argon environment with a moisture and oxygen content of <1 ppm. After injecting the electrolyte, the soft-pack lithium-ion battery was vacuum sealed and then mechanically pressed using a stamping tool with a standard shape. E) Electrochemical Measurement
[0173] The soft-pack lithium-ion battery was analyzed in constant current mode using a multi-channel battery tester (BTS-4008-5V10mA, from China Xinwei Electronics Co., Ltd.). After completing the initial cycle at C / 20, the discharge capacity was recorded. The button cell was then repeatedly charged and discharged at a rate of C / 2. The battery was tested for charge / discharge cycles at 25°C at a current density of C / 2 between 3.0 and 4.3V to obtain a capacity retention rate of 50 cycles. The electrochemical properties of the soft-pack lithium-ion battery of Example 1 are shown in Table 2 below. Preparation of polymer binders of Examples 2-12 and Comparative Examples 1-16, 19-20
[0174] A polymer binder was prepared in the same manner as in Example 1. Preparation of polymer binder of Example 13
[0175] The polymer binder was prepared in the same manner as in Example 1, except that 16.35 g NaOH was added when preparing the first suspension, 32.80 g acrylic acid was added when preparing the second suspension, 4.31 g acrylamide was added when preparing the third suspension, and 26.30 g acrylonitrile was added when preparing the fourth suspension. Preparation of polymer binder of Example 14
[0176] A polymer binder was prepared in the same manner as in Example 1, except that 8.26 g NaOH was added when preparing the first suspension, 18.22 g acrylic acid was added when preparing the second suspension, 13.66 g acrylamide was added when preparing the third suspension, and 30.06 g acrylonitrile was added when preparing the fourth suspension. Preparation of polymer binder of Example 15
[0177] The polymer binder was prepared in the same manner as in Example 1, except that 10.68 g NaOH was added when preparing the first suspension, 22.60 g acrylic acid was added when preparing the second suspension, 16.54 g acrylamide was added when preparing the third suspension, and 24.69 g acrylonitrile was added when preparing the fourth suspension. Preparation of polymer binder of Example 16
[0178] The polymer binder was prepared in the same manner as in Example 1, except that 10.28 g NaOH was added when preparing the first suspension, 21.87 g acrylic acid was added when preparing the second suspension, 5.03 g acrylamide was added when preparing the third suspension, and 33.81 g acrylonitrile was added when preparing the fourth suspension. Preparation of polymer binder of Comparative Example 17
[0179] A polymer binder was prepared in the same manner as in Example 1, except that 6.64 g NaOH was added when preparing the first suspension, 15.31 g acrylic acid was added when preparing the second suspension, 5.03 g acrylamide was added when preparing the third suspension, and 38.64 g acrylonitrile was added when preparing the fourth suspension.
[0180] Two more iterations of polymer binders were prepared by varying the ratio of monomer units in the polymer. In the first iteration, polyacrylamide was used as the polymer binder. In the second iteration, polyacrylonitrile was used as the polymer binder. In both iterations, the current collector and electrode material could not be separated due to the poor water solubility of the polymer binder. Preparation of polymer binder of Comparative Example 18
[0181] A polymer binder was prepared in the same manner as in Example 1, except that 2.19 g NaOH was added when preparing the first suspension, 7.29 g acrylic acid was added when preparing the second suspension, 17.97 g acrylamide was added when preparing the third suspension, and 34.89 g acrylonitrile was added when preparing the fourth suspension. Preparation of cathodes of Examples 2-16 and Comparative Examples 1-20
[0182] The cathodes were prepared by the method described in Example 1, except that the cathodes of Examples 2-16 and Comparative Examples 1-20 were prepared using the polymer binders prepared in Examples 2-16 and Comparative Examples 1-20, respectively. Recovery of the electrode of Example 2
[0183] The electrodes were recovered in the same manner as in Example 1, except that circulating water at 30° C. was used as the cleaning liquid. Recovery of the electrode of Example 3
[0184] The electrodes were recovered in the same manner as in Example 1, except that circulating water at 40° C. was used as the cleaning liquid. Recovery of the electrode of Example 4
[0185] The electrodes were recovered in the same manner as in Example 1, except that circulating water at 50° C. was used as the cleaning liquid. Recovery of the electrode of Example 5
[0186] The electrodes were recovered in the same manner as in Example 1, except that the current of the first ultrasonic generator and the second ultrasonic generator was 3A. Recovery of the electrode of Example 6
[0187] The electrodes were recovered in the same manner as in Example 1, except that the current of the first ultrasonic generator and the second ultrasonic generator was 4A. Recovery of the electrode of Example 7
[0188] The electrodes were recovered in the same manner as in Example 6, except that circulating water at 50° C. was used as the cleaning liquid. Recovery of the electrode of Example 8
[0189] The electrodes were recovered in the same manner as in Example 1, except that the current of the first ultrasonic generator and the second ultrasonic generator was 5A. Recovery of the electrode of Example 9
[0190] The electrodes were recovered in the same manner as in Example 6, except that the frequency of the first ultrasonic generator was 20 kHz. Recovery of the electrode of Example 10
[0191] The electrodes were recovered in the same manner as in Example 6, except that the frequency of the second ultrasonic generator was 45 kHz. Recovery of the electrode of Example 11
[0192] The electrode was recovered in the same manner as in Example 6, except that the time for the first ultrasonic cleaning was 30 seconds. Recovery of the electrode of Example 12
[0193] The electrode was recovered in the same manner as in Example 6, except that the time for the second ultrasonic cleaning was 20 seconds. Recovery of the electrodes of Examples 13-16
[0194] The electrode was recovered in the same manner as in Example 6. Recovery of the electrode of Comparative Example 1
[0195] The electrodes are recovered in the same manner as in Example 6, except that after the electrodes are sprayed and moistened with water by the first spray device, they are not subjected to the second ultrasonic cleaning by the second ultrasonic generator and the second rinsing by the second spray device, but are directly transported to the unloading platform to complete the entire cleaning process. The cleaned electrodes are dried by a drying device with room temperature and low wind speed to obtain a current collector.
[0196] The first ultrasonic cleaning time was increased to 65 seconds, and one more iteration of electrode recycling was performed. However, in this iteration, since only a single frequency was used for ultrasonic cleaning, the cleaning effect was poor, resulting in most of the electrode material remaining on the current collector surface. Recovery of the electrode of Comparative Example 2
[0197] The electrodes were recovered in the same manner as in Comparative Example 1, except that the current of the first ultrasonic generator was 5A. Recovery of the electrode of Comparative Example 3
[0198] The electrode was recovered in the same manner as in Comparative Example 1, except that circulating water at 50° C. was used as the cleaning liquid. Recovery of the electrode of Comparative Example 4
[0199] The electrodes were recovered in the same manner as in Comparative Example 3, except that the current of the first ultrasonic generator was 5A. Recovery of the electrode of Comparative Example 5
[0200] The electrodes were recovered in the same manner as in Comparative Example 1, except that the frequency of the first ultrasonic generator was 38 kHz.
[0201] The first ultrasonic cleaning time was increased to 65 seconds, and one more iteration of electrode recycling was performed. However, in this iteration, since only a single frequency was used for ultrasonic cleaning, the cleaning effect was poor, resulting in most of the electrode material remaining on the current collector surface. Recovery of the electrode of Comparative Example 6
[0202] The electrodes were recovered in the same manner as in Comparative Example 5, except that the current of the first ultrasonic generator was 5A. Recovery of the electrode of Comparative Example 7
[0203] The electrode was recovered in the same manner as in Comparative Example 5, except that circulating water at 50° C. was used as the cleaning liquid. Recovery of the electrode of Comparative Example 8
[0204] The electrodes were recovered in the same manner as in Comparative Example 7, except that the current of the first ultrasonic generator was 5A. Recovery of the electrode of Comparative Example 9
[0205] The electrode was recovered in the same manner as in Example 6, except that circulating water at 60° C. was used as the cleaning liquid. Recovery of the electrode of Comparative Example 10
[0206] The electrode was recovered in the same manner as in Example 6, except that circulating water at 70° C. was used as the cleaning liquid. Recovery of the electrode of Comparative Example 11
[0207] The electrodes were recovered in the same manner as in Example 1, except that the current of the first ultrasonic generator and the second ultrasonic generator was 6A. Recovery of the electrode of Comparative Example 12
[0208] The electrode was recovered in the same manner as in Example 6, except that the time for the first ultrasonic cleaning was 50 seconds. Recovery of the electrode of Comparative Example 13
[0209] The electrode was recovered in the same manner as in Example 6, except that the time for the second ultrasonic cleaning was 30 seconds. Recovery of the electrode of Comparative Example 14
[0210] The electrode was recovered in the same manner as in Example 6, except that the time for the first ultrasonic cleaning was 20 seconds. Recovery of the electrode of Comparative Example 15
[0211] The electrode was recovered in the same manner as in Example 6, except that the time for the second ultrasonic cleaning was 10 seconds. Recovery of the electrode of Comparative Example 16
[0212] The electrodes were recovered in the same manner as in Example 6, except that the frequency of the first ultrasonic generator was 38 kHz and the frequency of the second ultrasonic generator was 28 kHz. Recovery of electrodes of Comparative Examples 17-18 and 20
[0213] The electrode was recovered in the same manner as in Example 6. Preparation of soft-pack lithium-ion batteries of Examples 6-7, 9-14
[0214] The soft-pack lithium-ion batteries were prepared by the method described in Example 1, except that the cathode materials and conductive agents recovered and filtered in Examples 6-7 and 9-14 were used to prepare the soft-pack lithium-ion batteries of Examples 6-7 and 9-14, respectively. Preparation of soft-pack lithium-ion battery of Comparative Example 19
[0215] A soft-pack lithium-ion battery was prepared by the method described in Example 1, except that when preparing the cathode, the cathode material and conductive agent material used did not undergo a recycling process, but the cathode prepared in Comparative Example 19 was directly used to prepare the soft-pack lithium-ion battery of Comparative Example 19. Preparation of soft-pack lithium-ion battery of Comparative Example 20
[0216] A soft-pack lithium-ion battery was prepared by the method described in Example 1, except that, when preparing the cathode, a mixture of 138 g of unused LiFePO4 and 138 g of the cathode material recovered by filtration in Comparative Example 20 was used. The mixture was then added to the first mixture to prepare the soft-pack lithium-ion battery of Comparative Example 20. Electrochemical measurements of Examples 6-7, 9-14 and Comparative Examples 19-20
[0217] The electrochemical properties of the soft-pack lithium-ion batteries of Examples 6-7, 9-14 and Comparative Examples 19-20 were measured in the same manner as in Example 1, and the test results are shown in Table 2 below.
[0218] Although the present invention has been described in conjunction with a limited number of embodiments, the specific features of one embodiment should not limit other embodiments of the present invention. In some embodiments, the method may include a plurality of steps that the present invention does not mention. In other embodiments, the method does not include or substantially does not contain any steps that the present invention does not enumerate. There are variations and changes based on the described embodiments. The attached claims are intended to cover all these variations and changes that fall within the scope of the present invention.
Claims
1. A method for recycling battery electrodes, comprising the following steps: a) wetting an electrode comprising a current collector and an electrode layer coated on one or both sides of the current collector with a cleaning solution; b) immersing the electrode in a cleaning solution and performing a first ultrasonic cleaning; c) taking out the electrode and rinsing it with a cleaning solution for the first time; d) immersing the electrode in a cleaning solution and performing a second ultrasonic cleaning; e) taking out the electrode and rinsing it for a second time with a cleaning solution to remove the electrode layer peeled off from the surface of its current collector; The electrode layer comprises a polymer binder and an electrode active material. The method according to claim 1 , wherein the cleaning fluid is water.
3. The method of claim 1, wherein the cleaning solution is an aqueous solvent comprising a major component and a minor component.
4. The method of claim 3, wherein the major component is water; and wherein the minor component is selected from the group consisting of methanol, ethanol, isopropanol, n-propanol, tert-butanol, n-butanol, dimethylacetamide, dimethylformamide, N-methylpyrrolidone, methyl ethyl ketone, ethyl acetate, butyl acetate, and combinations thereof.
5. The method of claim 1, wherein the cleaning solution has a temperature of about 10°C to about 50°C. The method according to claim 1 , wherein the wetting is performed using an atomizing spray nozzle. The method according to claim 1 , wherein a shower head is used to rinse the electrode during the first rinsing and the second rinsing.
8. The method according to claim 1, wherein in the first ultrasonic cleaning and the second ultrasonic cleaning, an ultrasonic generator is used to generate ultrasonic waves to clean the electrode.
9. The method according to claim 8, wherein the ultrasonic generators are each selected from an ultrasonic bath, a probe-type ultrasonic generator, an ultrasonic flow cell, an ultrasonic vibration plate, an ultrasonic vibrator, and a combination thereof.
10. The method of claim 1, wherein the frequency used in the first ultrasonic cleaning is about 20 kHz to about 30 kHz.
11. The method according to claim 1, wherein the current used in the first ultrasonic cleaning is about 2A to about 5A.
12. The method according to claim 1, wherein the first ultrasonic cleaning is performed for a period of about 20 to about 40 seconds.
13. The method of claim 1, wherein the frequency used in the second ultrasonic cleaning is about 35 kHz to about 45 kHz.
14. The method according to claim 1, wherein the current used in the second ultrasonic cleaning is about 2A to about 5A.
15. The method according to claim 1, wherein the second ultrasonic cleaning is performed for a period of about 20 to about 25 seconds.
16. The method according to claim 1, wherein the solid-liquid ratio of the cleaning solution is less than 30%.
17. A battery electrode recovery device, characterized in that: The invention comprises a casing, wherein a conveying device is arranged inside the casing, wherein the conveying device comprises a motor, a rotating shaft and a conveying belt, wherein the conveying belt is mounted on the rotating shaft, and driven by the motor, the battery electrodes on the conveying belt pass through a first spraying device, a first groove, a second spraying device, a second groove and a third spraying device arranged inside the casing, wherein an ultrasonic generating device is arranged at the bottom of the first groove and the second groove, and wherein the device implements the steps of the battery electrode recycling method as described in any one of claims 1 to 16.
18. The device according to claim 17, characterized in that The first groove and / or the second groove is provided with a heating device.
Citation Information
Patent Citations
Method for separating and recycling current collector and negative electrode material in negative electrode of waste lithium ion battery
CN114665182A